Polytetrafluoroethylene, binder for electrochemical device, electrode mixture, electrode, and secondary battery

Polytetrafluoroethylene with specific surface areas and particle sizes is used to address the fibrous nature of existing binders, improving handling and reducing production costs by minimizing feeder clogging and dispersion medium use, while enhancing binding strength in electrochemical devices.

JP2025010043AActive Publication Date: 2025-01-20DAIKIN INDUSTRIES LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024105284
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-28
Publication Date
2025-01-20
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

Existing binders for electrochemical devices, such as polytetrafluoroethylene, tend to become fibrous during transportation and are difficult to handle, leading to feeder clogging and increased production costs due to the need for large amounts of dispersion media.

Method used

The use of polytetrafluoroethylene with specific surface areas between 0.5 m²/g and 7.0 m²/g, containing 40% by mass or more of polytetrafluoroethylene particles with a particle size of 1 μm or more, produced by suspension polymerization, which has low fibrillation properties and is easier to feed, reducing the need for dispersion media and improving binding strength.

Benefits of technology

The solution prevents feeder clogging, reduces the amount of dispersion medium required, and enhances the binding strength of active materials and electrolytes, thereby simplifying the production process and lowering costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010043000001_ABST
    Figure 2025010043000001_ABST
Patent Text Reader

Abstract

To provide: polytetrafluoroethylene for a binder for electrochemical devices, which is easily fed and unlikely to fiberized during transport; and a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery in which the polytetrafluoroethylene is used.SOLUTION: There is provided polytetrafluoroethylene used for a binder for electrochemical devices, the polytetrafluoroethylene having a specific surface area of 0.5 m2 / g or more and less than 7.0 m2 / g.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polytetrafluoroethylene, a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery. [Background technology]

[0002] Secondary batteries such as lithium-ion secondary batteries are used in small, portable electric and electronic devices such as notebook computers, mobile phones, smartphones, tablet computers, and ultrabooks, due to their high voltage, high energy density, low self-discharge, low memory effect, and the ability to be made extremely lightweight, and are also being put into practical use as a wide range of power sources, including on-board power sources for driving automobiles and large stationary power sources. There is a demand for secondary batteries to have even higher energy density, and further improvements in their battery characteristics are required.

[0003] Patent Document 1 describes an energy storage device in which at least one of the cathode and the anode contains a polytetrafluoroethylene composite binder material.

[0004] Patent Documents 2 to 6 describe the use of polytetrafluoroethylene as a binder for batteries.

[0005] Patent Document 7 describes the use of a mixture of polytetrafluoroethylene and polyvinylidene fluoride as a binder for batteries. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2017-517862 [Patent Document 2] International Publication No. 2021 / 181887 [Patent Document 3] International Publication No. 2021 / 181888 [Patent Document 4] International Publication No. 2021 / 192541 [Patent Document 5] International Publication No. 2022 / 138942 [Patent Document 6] International Publication No. 2022 / 138939 [Patent Document 7] International Publication No. 2022 / 234227 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present disclosure is to provide polytetrafluoroethylene for binders for electrochemical devices that is less likely to become fibrous during transportation and is easy to feed, as well as a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery that use the same. [Means for solving the problem]

[0008] The present disclosure (1) relates to polytetrafluoroethylene used as a binder for electrochemical devices, Specific surface area is 0.5m 2 / g or more 7.0m 2 / g.

[0009] This disclosure (2) has a specific surface area of ​​1.5 m 2 / g or more 5.5m 2 / g or less, and a standard specific gravity of 2.150 or more and 2.160 or less.

[0010] The present disclosure (3) is a binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 / g.

[0011] The present disclosure (4) relates to a method for producing polytetrafluoroethylene having a specific surface area of ​​1.5 m 2 / g or more 5.5m 2 / g or less, and a standard specific gravity of 2.150 or more and 2.160 or less.

[0012] The present disclosure (5) relates to polytetrafluoroethylene used as a binder for electrochemical devices, Specific surface area 0.5m 2 / g or more 7.0m 2 / g.

[0013] This disclosure (6) has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 The polytetrafluoroethylene according to the present disclosure (5) contains 40 mass % or more of polytetrafluoroethylene having a standard specific gravity of 2.150 or more and 2.160 or less.

[0014] The present disclosure (7) is a binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 The binder for electrochemical devices contains 40 mass % or more of polytetrafluoroethylene, the content of which is less than 1 / g.

[0015] In the present disclosure (8), the polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 The binder for electrochemical devices according to the present disclosure (7) contains 40 mass % or more of polytetrafluoroethylene with a molecular weight of less than 100 / g and has a standard specific gravity of 2.150 or more and 2.160 or less.

[0016] The present disclosure (9) relates to polytetrafluoroethylene used as a binder for electrochemical devices, The polytetrafluoroethylene contains 40% by mass or more of polytetrafluoroethylene obtained by suspension polymerization.

[0017] The present disclosure (10) relates to a binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene is a binder for electrochemical devices containing 40% by mass or more of polytetrafluoroethylene obtained by suspension polymerization.

[0018] The present disclosure (11) relates to polytetrafluoroethylene used as a binder for electrochemical devices, The polytetrafluoroethylene contains 40 mass % or more of polytetrafluoroethylene including polytetrafluoroethylene particles with a particle diameter of 1 μm or more.

[0019] The present disclosure (12) is the polytetrafluoroethylene according to the present disclosure (9) or (11), having a standard specific gravity of 2.150 or more and 2.160 or less.

[0020] The present disclosure (13) is a binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene is a binder for electrochemical devices containing 40 mass % or more of polytetrafluoroethylene containing polytetrafluoroethylene particles having a particle diameter of 1 μm or more.

[0021] The present disclosure (14) relates to the binder for electrochemical devices according to the present disclosure (3), (4), (7), (8), (10) or (13), wherein the polytetrafluoroethylene is polytetrafluoroethylene that does not exhibit melt flowability.

[0022] The present disclosure (15) is the binder for electrochemical devices according to the present disclosure (3), (4), (7), (8), (10), (13) or (14), wherein the polytetrafluoroethylene has an endothermic peak temperature of 333° C. or higher.

[0023] The present disclosure (16) is the binder for electrochemical devices according to any one of the present disclosures (3), (7), (10), and (13) to (15), wherein the polytetrafluoroethylene has a standard specific gravity of 2.130 or more and 2.230 or less.

[0024] The present disclosure (17) is the binder for electrochemical devices according to any one of the present disclosures (3), (7), (10), and (13) to (16), wherein the polytetrafluoroethylene has a standard specific gravity of 2.150 or more and 2.160 or less.

[0025] The present disclosure (18) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (17), wherein the polytetrafluoroethylene is polytetrafluoroethylene that does not substantially use a fluorine-containing compound having a molecular weight of 1,000 or less during polymerization.

[0026] The present disclosure (19) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (18), wherein the polytetrafluoroethylene contains polytetrafluoroethylene obtained by suspension polymerization.

[0027] The present disclosure (20) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (19), wherein the polytetrafluoroethylene is not paste extrudable.

[0028] The present disclosure (21) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (20), wherein the polytetrafluoroethylene is a powder.

[0029] The present disclosure (22) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (21), wherein the polytetrafluoroethylene is substantially free of moisture.

[0030] The present disclosure (23) is the binder for electrochemical devices according to any one of the present disclosures (3), (4), (7), (8), (10), and (13) to (22), wherein the polytetrafluoroethylene is substantially free of a fluorine-containing compound having a molecular weight of 1,000 or less.

[0031] The present disclosure (24) is an electrode mixture comprising the polytetrafluoroethylene according to the present disclosure (1), (2), (5), (6), (9), (11) or (12), or the binder for electrochemical device according to any one of the present disclosures (3), (4), (7), (8), (10), (13) to (23), and an electrode active material.

[0032] The present disclosure (25) is an electrode mixture according to the present disclosure (24) which is a sheet.

[0033] The present disclosure (26) is an electrode comprising the polytetrafluoroethylene according to the present disclosure (1), (2), (5), (6), (9), (11) or (12), or the binder for electrochemical device according to any one of the present disclosures (3), (4), (7), (8), (10), (13) to (23), an electrode active material, and a current collector.

[0034] The present disclosure (27) is a secondary battery including the electrode according to the present disclosure (26). Effect of the Invention

[0035] According to the present disclosure, it is possible to provide polytetrafluoroethylene for binders for electrochemical devices that is less likely to become fibrous during transportation and is easy to feed, as well as a binder for electrochemical devices, an electrode mixture, an electrode, and a secondary battery each using the polytetrafluoroethylene. [Brief description of the drawings]

[0036] [Figure 1] 1 shows the appearance of electrodes when evaluating dispersion defects in Examples, the left side being the electrode of Comparative Example 3 and the right side being the electrode of Example 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The present disclosure will now be described in detail.

[0038] The present disclosure relates to a polytetrafluoroethylene (PTFE) used as a binder for electrochemical devices, the specific surface area of ​​which is less than 0.5 m 2 / g or more 7.0m 2 / g (hereinafter, also referred to as PTFE (1) of the present disclosure).

[0039] The present disclosure relates to a PTFE having a specific surface area of ​​0.5 m for use in a binder for an electrochemical device. 2 / g or more 7.0m 2 The present invention also provides a PTFE containing 40 mass % or more of polytetrafluoroethylene with a molecular weight of less than 1000 / g (hereinafter also referred to as PTFE (2) of the present disclosure).

[0040] The present disclosure also provides a PTFE used in a binder for an electrochemical device, the PTFE containing 40 mass % or more of PTFE obtained by suspension polymerization (hereinafter also referred to as PTFE (3) of the present disclosure).

[0041] The present disclosure also provides PTFE for use in a binder for electrochemical devices, the PTFE containing 40 mass % or more of polytetrafluoroethylene containing PTFE particles having a particle diameter of 1 μm or more (hereinafter also referred to as PTFE (4) of the present disclosure).

[0042] In this specification, unless otherwise specified, PTFEs (1) to (4) of the present disclosure will be collectively referred to as "PTFE of the present disclosure."

[0043] The PTFE of the present disclosure has the above-mentioned structure, and is less likely to be fibrous during transportation, making feeding easy. In particular, when feeding using a feeder, clogging of the feeder (adhesion to the feeder) is less likely to occur. Furthermore, cleaning work for dismantling the feeder can be reduced. The feeder may be, for example, a screw feeder equipped with an internal hopper and a feed screw (such as the Accurate Feeder manufactured by Schenck Accurate Co., Ltd.). The PTFE of the present disclosure can suppress adhesion to the internal hopper and the feed screw.

[0044] The PTFE of the present disclosure is also advantageous in terms of production process since it does not require the use of a large amount of a dispersion medium such as water or an organic solvent, and a wide range of electrode active materials and solid electrolytes can be selected for combination. In addition, the process and cost involved in using a dispersion medium can be reduced. Furthermore, since the PTFE of the present disclosure has excellent binding strength with active materials and electrolytes, the amount of PTFE used can be reduced.

[0045] The PTFE (1) disclosed herein has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 / g. Specific surface area: 0.5 m 2 / g or more 7.0m 2 PTFE with a viscosity of less than 1000 μm / g has low fibrillation properties, so it is less likely to become fibrous during transportation and is easier to feed. The specific surface area is 1.0 m 2 / g or more, and 1.5m 2 / g or more is more preferable, and 6.5m 2 / g or less, and 6.0m 2 / g or less is more preferable, and 5.5m 2 More preferably, it is 5.0m / g or less. 2 More preferably, the ratio is 4.5m / g or less. 2 More preferably, the ratio is 4.0m / g or less. 2 More preferably, the ratio is 3.5m / g or less. 2 It is even more preferable that the value is 3.0m / g or less. 2 More preferably, it is 2.5m / g or less. 2 It is even more preferable that the molecular weight is not more than 1 / g. The specific surface area can be measured by the BET method in accordance with JIS Z8830 using a mixed gas of 30% nitrogen and 70% helium as a carrier gas and cooling with liquid nitrogen.

[0046] The PTFE (1) of the present disclosure is less likely to become fibrous during transportation and is easier to feed, so it preferably contains PTFE particles with a particle diameter of 1 μm or more, more preferably contains PTFE particles with a particle diameter of 5 μm or more, even more preferably contains PTFE particles with a particle diameter of 10 μm or more, even more preferably contains PTFE particles with a particle diameter of 15 μm or more, and particularly preferably contains PTFE particles with a particle diameter of 20 μm or more, and preferably contains PTFE particles with a particle diameter of 500 μm or less, more preferably contains PTFE particles with a particle diameter of 400 μm or less, even more preferably contains PTFE particles with a particle diameter of 300 μm or less, even more preferably contains PTFE particles with a particle diameter of 200 μm or less, and particularly preferably contains PTFE particles with a particle diameter of 100 μm or less. The presence or absence of PTFE particles with a particle size of 1 μm or more can be confirmed by determining the particle size of the PTFE particles through observation using a scanning electron microscope (SEM). The particle size is determined by taking an SEM image of the PTFE powder at a magnification of 2000 times and measuring the distance between two horizontal parallel lines that sandwich the particle. The PTFE (1) of the present disclosure may be PTFE that does not contain PTFE particles with a particle size of less than 1 μm.

[0047] The PTFE (1) of the present disclosure has a median diameter (d50) of preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more. Also, it is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 100 μm or less. The median diameter is determined by the following laser diffraction method. This is done in a dry state using a HELOS&RODOS system (product name, manufactured by SYMPATEC). The powder to be measured is dispersed with compressed air at a dispersion pressure of 2 bar, and the shadow of the powder to be measured, projected by a laser, is detected by the measurement sensor unit to calculate the particle size distribution of the powder to be measured, and the average particle size (50% cumulative particle size) d50 is determined on a volume basis. d50 is equal to the particle size corresponding to 50% of the cumulative particle size distribution.

[0048] The PTFE (1) of the present disclosure can be produced by suspension polymerization. The PTFE (1) of the present disclosure preferably contains PTFE obtained by suspension polymerization, and preferably consists of only PTFE obtained by suspension polymerization. The specific surface area of ​​PTFE obtained by suspension polymerization is usually lower than that of PTFE obtained by emulsion polymerization.

[0049] In this specification, the suspension polymerization is polymerization carried out in an aqueous medium in the absence of a surfactant or in the presence of 2000 mass ppm or less of a surfactant relative to the aqueous medium. The details of the suspension polymerization will be described later.

[0050] In this specification, "PTFE particles having a particle size of 1 μm or more" refers to PTFE particles produced by suspension polymerization. PTFE particles produced by suspension polymerization are usually scaly in shape as described below, and can be visually distinguished from secondary particles of PTFE particles produced by emulsion polymerization.

[0051] The PTFE particles having a particle size of 1 μm or more are usually scaly PTFE particles.

[0052] The PTFE particles having a particle diameter of 1 μm or more preferably have a ratio of diameter to thickness (diameter / thickness) of 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, and preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less. The above ratio is determined by observing the PTFE particles with a scanning electron microscope (SEM), processing the images, and calculating the diameter and thickness. The ratio is determined for 20 particles, and the average value is used.

[0053] The PTFE (2) disclosed herein has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 / g. Specific surface area: 0.5 m 2 / g or more 7.0m 2 Since PTFE with a concentration of less than 1000 g / g has low fibrillation properties, the presence of this specific proportion of PTFE makes it difficult for the PTFE to become fibrillated during transportation and facilitates feeding. The specific surface area is 1.0 m 2 / g or more, and 1.5m 2 / g or more is more preferable, and 6.5m 2 / g or less, and 6.0m 2 / g or less is more preferable, and 5.5m 2 More preferably, it is 5.0m / g or less. 2 More preferably, the ratio is 4.5m / g or less. 2 More preferably, the ratio is 4.0m / g or less. 2 More preferably, the ratio is 3.5m / g or less. 2 It is even more preferable that the value is 3.0m / g or less. 2 More preferably, it is 2.5m / g or less. 2 It is even more preferable that the molecular weight is not more than 1 / g.

[0054] In the PTFE (2) of the present disclosure, the specific surface area of ​​0.5 m 2 / g or more 7.0m 2 A PTFE content of less than 1 / g is preferably 45% by mass or more, more preferably 50% by mass or more, even more preferably more than 50% by mass, still more preferably 55% by mass or more, particularly preferably 60% by mass or more, and may be 100% by mass or less, in that the PTFE is less likely to become fibrous during transportation and easier to feed.

[0055] The specific surface area of ​​0.5m 2 / g or more 7.0m 2 PTFE having a particle diameter of less than 1 μm / g is less likely to become fibrous during transportation and easier to feed, and therefore preferably contains PTFE particles with a particle diameter of 1 μm or more, more preferably contains PTFE particles with a particle diameter of 5 μm or more, even more preferably contains PTFE particles with a particle diameter of 10 μm or more, even more preferably contains PTFE particles with a particle diameter of 15 μm or more, and particularly preferably contains PTFE particles with a particle diameter of 20 μm or more, and preferably contains PTFE particles with a particle diameter of 500 μm or less, more preferably contains PTFE particles with a particle diameter of 400 μm or less, even more preferably contains PTFE particles with a particle diameter of 300 μm or less, even more preferably contains PTFE particles with a particle diameter of 200 μm or less, and particularly preferably contains PTFE particles with a particle diameter of 100 μm or less. The specific surface area of ​​0.5m 2 / g or more 7.0m 2 / g may be PTFE that does not contain PTFE particles having a particle size of less than 1 μm.

[0056] The specific surface area of ​​0.5m 2 / g or more 7.0m 2 For PTFE with a molecular weight of less than 100 μm / g, the median diameter (d50) is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more, and is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 100 μm or less.

[0057] The specific surface area of ​​0.5m 2 / g or more 7.0m 2 PTFE having a specific surface area of ​​less than 1 / g can be produced by suspension polymerization. The PTFE (2) of the present disclosure preferably contains PTFE obtained by suspension polymerization. The specific surface area of ​​PTFE obtained by suspension polymerization is usually lower than that of PTFE obtained by emulsion polymerization.

[0058] The PTFE (2) of the present disclosure has a specific surface area of ​​7.0 m 2 The specific surface area may be 0.5 m 2 / g or more 7.0m 2 / g and a specific surface area of ​​7.0 m 2 The mass ratio of PTFE to fluororesin is preferably 40 / 60 or more, more preferably 45 / 55 or more, even more preferably 50 / 50 or more, even more preferably more than 50 / 50, even more preferably 55 / 45 or more, and particularly preferably 60 / 40 or more.

[0059] The specific surface area is 7.0m 2 PTFE having a molecular weight of 1.0 to 1.0 g / g or more can be produced by emulsion polymerization, the details of which will be described later.

[0060] The PTFE (3) of the present disclosure contains 40% by mass or more of PTFE obtained by suspension polymerization. Since the PTFE obtained by suspension polymerization has low fibrillation properties, the presence of a specific proportion of the PTFE makes it difficult for the PTFE to become fibrous during transportation, making feeding easy.

[0061] In the PTFE (3) of the present disclosure, the content of the PTFE obtained by the suspension polymerization is preferably 45% by mass or more, more preferably 50% by mass or more, even more preferably more than 50% by mass, even more preferably 55% by mass or more, particularly preferably 60% by mass or more, and may be 100% by mass or less, based on the PTFE, in that the PTFE is less likely to become fibrous during transportation and is easier to feed. The content of PTFE obtained by the above suspension polymerization was 0.5 m 2 / g or more 7.0m 2 / g PTFE content.

[0062] The PTFE obtained by the above suspension polymerization is less likely to become fibrous during transportation and is easier to feed, so it preferably contains PTFE particles with a particle diameter of 1 μm or more, more preferably contains PTFE particles with a particle diameter of 5 μm or more, even more preferably contains PTFE particles with a particle diameter of 10 μm or more, even more preferably contains PTFE particles with a particle diameter of 15 μm or more, and particularly preferably contains PTFE particles with a particle diameter of 20 μm or more, and preferably contains PTFE particles with a particle diameter of 500 μm or less, more preferably contains PTFE particles with a particle diameter of 400 μm or less, even more preferably contains PTFE particles with a particle diameter of 300 μm or less, even more preferably contains PTFE particles with a particle diameter of 200 μm or less, and particularly preferably contains PTFE particles with a particle diameter of 100 μm or less. The PTFE obtained by the above suspension polymerization may be PTFE that does not contain PTFE particles with a particle size of less than 1 μm.

[0063] The PTFE obtained by the above suspension polymerization has a median diameter (d50) of preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more, and preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 100 μm or less.

[0064] The PTFE obtained by the above suspension polymerization is more difficult to become fibrous during transportation and is easier to feed, and is therefore more suitable for use with a specific surface area of ​​0.5 m. 2 / g or more, and 1.0m 2 / g or more is more preferable, and 1.5m 2 / g or more is more preferable, and 7.0m 2 / g, and preferably less than 6.5m 2 / g or less is more preferable, and 6.0m 2 More preferably, it is 5.5m / g or less. 2 It is even more preferable that the value is 5.0m / g or less. 2More preferably, the ratio is 4.5m / g or less. 2 More preferably, the ratio is 4.0m / g or less. 2 More preferably, the ratio is 3.5m / g or less. 2 It is even more preferable that the value is 3.0m / g or less. 2 More preferably, it is 2.5m / g or less. 2 It is even more preferable that the molecular weight is not more than 1 / g.

[0065] The PTFE (3) of the present disclosure may further contain PTFE obtained by emulsion polymerization. The mass ratio of the PTFE obtained by suspension polymerization to the PTFE obtained by emulsion polymerization is preferably 40 / 60 or more, more preferably 45 / 55 or more, even more preferably 50 / 50 or more, even more preferably more than 50 / 50, even more preferably 55 / 45 or more, and particularly preferably 60 / 40 or more.

[0066] The PTFE (4) of the present disclosure contains 40% by mass or more of PTFE containing PTFE particles having a particle diameter of 1 μm or more. Since PTFE containing PTFE particles having a particle diameter of 1 μm or more has low fibrillation properties, the presence of a specific proportion of the PTFE makes it difficult for the PTFE to become fibrous during transportation, making feeding easier. The PTFE preferably contains PTFE particles of 5 μm or more, more preferably contains PTFE particles of 10 μm or more, even more preferably contains PTFE particles of 15 μm or more, and particularly preferably contains PTFE particles of 20 μm or more, and preferably contains PTFE particles of 500 μm or less, more preferably contains PTFE particles of 400 μm or less, even more preferably contains PTFE particles of 300 μm or less, even more preferably contains PTFE particles of 200 μm or less, and particularly preferably contains PTFE particles of 100 μm or less. The PTFE containing PTFE particles with a particle size of 1 μm or more may be PTFE that does not contain PTFE particles with a particle size of less than 1 μm.

[0067] The PTFE containing the PTFE particles having a particle diameter of 1 μm or more preferably has a median diameter (d50) of 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more. It is also preferable that the median diameter (d50) is 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 100 μm or less.

[0068] In the PTFE (4) of the present disclosure, the content of PTFE including the PTFE particles having a particle size of 1 μm or more is preferably 45% by mass or more, more preferably 50% by mass or more, even more preferably more than 50% by mass, even more preferably 55% by mass or more, particularly preferably 60% by mass or more, and may be 100% by mass or less, in that the PTFE is less likely to become fibrous during transportation and is easier to feed. The content of PTFE containing the above-mentioned PTFE particles having a particle diameter of 1 μm or more is 2 / g or more 7.0m 2 / g and equal to the PTFE content obtained in the suspension polymerization.

[0069] PTFE containing PTFE particles with a particle diameter of 1 μm or more is less likely to become fibrous during transportation and is easier to feed, and is therefore preferred over PTFE containing PTFE particles with a specific surface area of ​​0.5 m. 2 / g or more, and 1.0m 2 / g or more is more preferable, and 1.5m 2 / g or more is more preferable, and 7.0m 2 / g, and preferably less than 6.5m 2 / g or less is more preferable, and 6.0m 2 More preferably, it is 5.5m / g or less. 2 It is even more preferable that the value is 5.0m / g or less. 2 More preferably, the ratio is 4.5m / g or less. 2More preferably, the ratio is 4.0m / g or less. 2 More preferably, the ratio is 3.5m / g or less. 2 It is even more preferable that the value is 3.0m / g or less. 2 More preferably, it is 2.5m / g or less. 2 It is even more preferable that the molecular weight is not more than 1 / g.

[0070] The PTFE containing PTFE particles having a particle size of 1 μm or more can be produced by suspension polymerization. The PTFE (4) of the present disclosure preferably contains PTFE obtained by suspension polymerization. The particle size of the PTFE obtained by suspension polymerization is usually larger than that of the PTFE obtained by emulsion polymerization.

[0071] The PTFE (2) of the present disclosure may further contain PTFE that does not contain PTFE particles having a particle size of 1 μm or more. The mass ratio of the PTFE containing PTFE particles having a particle size of 1 μm or more to the PTFE not containing PTFE particles having a particle size of 1 μm or more is preferably 40 / 60 or more, more preferably 45 / 55 or more, even more preferably 50 / 50 or more, even more preferably more than 50 / 50, even more preferably 55 / 45 or more, and particularly preferably 60 / 40 or more.

[0072] The PTFE that does not contain PTFE particles having a particle size of 1 μm or more can be produced by emulsion polymerization.

[0073] The PTFE of the present disclosure may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing polymerization units based on TFE (TFE units) and polymerization units based on a modified monomer copolymerizable with TFE (hereinafter also referred to as "modified monomer units"). The above-mentioned TFE homopolymer refers to one in which the content of modified monomer units relative to the total polymerized units is less than 0.0001% by mass. The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units, or may consist of only TFE units and modified monomer units.

[0074] The modified PTFE is less likely to be fibrous during transportation and easier to feed, so the content of the modified monomer unit is preferably in the range of 0.0001 to 1.0% by mass relative to the total polymerized units. The lower limit of the content of the modified monomer unit is more preferably 0.001% by mass, more preferably 0.010% by mass, even more preferably 0.015% by mass, even more preferably 0.020% by mass, and particularly preferably 0.050% by mass. The upper limit of the content of the modified monomer unit is preferably 0.80% by mass, more preferably 0.60% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, and particularly preferably 0.20% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0075] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0076] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0077] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf1 (A) (In the formula, Rf 1 represents a perfluoro organic group. ) and the like. In this specification, the above-mentioned "perfluoro organic group" means an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.

[0078] The perfluorovinyl ether may be, for example, a compound represented by the general formula (A) in which Rf 1 and perfluoro(alkyl vinyl ether) [PAVE], which is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0079] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0080] The perfluorovinyl ether further includes, in the above general formula (A), Rf 1 is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, Rf 1 is the following formula:

[0081] [ka]

[0082] (wherein m represents 0 or an integer of 1 to 4), Rf 1 is the following formula:

[0083] [ka]

[0084] (wherein n represents an integer of 1 to 4).

[0085] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0086] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 2 (B) (In the formula, Rf 2 represents a perfluoro organic group.

[0087] Above Rf 2 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.

[0088] The modified monomer is represented by the following general formula (I): CX 1 X 2 =CX 3 X 4 (I) (In the formula, X 1 ~X 3 are each independently H or F. 4 is F, Cl, Rf or O-Rf. Rf is a perfluoro organic group.

[0089] Rf in general formula (I) is preferably a perfluoroalkyl group having 1 to 10 carbon atoms, more preferably a perfluoroalkyl group having 1 to 5 carbon atoms, and even more preferably a perfluoroalkyl group having 1 to 4 carbon atoms.

[0090] In terms of being less likely to become fibrous during transportation and being easier to feed, the modified monomer is preferably at least one selected from the group consisting of CTFE, HFP, perfluoro(methyl vinyl ether) [PMVE], perfluoro(propyl vinyl ether) [PPVE], PFBE and VDF, more preferably at least one selected from the group consisting of CTFE, HFP, PMVE and PPVE, even more preferably at least one selected from the group consisting of CTFE, HFP and PPVE, and particularly preferably at least one selected from the group consisting of PPVE and HFP.

[0091] The PTFE of the present disclosure may have a core-shell structure. For example, the PTFE having the core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, such modified PTFE may be PTFE described in JP-A-2005-527652.

[0092] The PTFE of the present disclosure is preferably a PTFE that does not exhibit melt flowability. In this specification, not exhibiting melt fluidity means that the melt flow rate (MFR) is less than 0.25 g / 10 min, preferably less than 0.10 g / 10 min, more preferably 0.05 g / 10 min or less, and even more preferably 0.01 g / 10 min or less. The MFR is a value obtained in accordance with ASTM D1238 using a melt indexer, and is expressed as the mass (g / 10 min) of polymer flowing out per 10 min from a nozzle having an inner diameter of 2.095 mm and a length of 8 mm at 372° C. and a load of 5 kg.

[0093] The PTFE of the present disclosure is less likely to become fibrous during transportation and is easier to feed, so that the endothermic peak temperature is preferably 333°C or higher, more preferably 335°C or higher, and even more preferably 337°C or higher, and is preferably 350°C or lower, and more preferably 346°C or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, the temperature corresponding to the minimum value is taken as the endothermic peak temperature.

[0094] The PTFE of the present disclosure is preferably substantially free of moisture. This can suppress gas generation and deterioration of electrochemical device properties. In addition, it is advantageous in terms of production process because it allows a wide range of electrode active materials and solid electrolytes to be combined. "Substantially free of moisture" means that the moisture content of the PTFE is 0.010% by mass or less. The water content is preferably 0.005% by mass or less, more preferably 0.003% by mass or less, even more preferably 0.002% by mass or less, and even more preferably 0.001% by mass or less. The water content is measured by the following method. The mass of the PTFE is measured before and after heating at 150°C for 2 hours, and calculated according to the following formula. Samples are taken three times, and the mass is calculated for each time, and the average value is calculated and used. Moisture content (mass%) = [(mass of PTFE before heating (g)) - (mass of PTFE after heating (g))] / (mass of PTFE before heating (g)) x 100

[0095] The PTFE of the present disclosure is preferably one that does not substantially use a fluorine-containing compound having a molecular weight of 1000 or less during polymerization. Substantially not using a fluorine-containing compound having a molecular weight of 1000 or less means that the amount of the fluorine-containing compound used is 100 mass ppm or less relative to the aqueous medium. The amount used is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, even more preferably 10 mass ppm or less, and most preferably 0 mass ppm, that is, no fluorine-containing compound is used at all. The fluorine-containing compound having a molecular weight of 1,000 or less will be described later.

[0096] The PTFE of the present disclosure is preferably substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably 20 mass ppb or less, more preferably 15 mass ppb or less, even more preferably 10 mass ppb or less, even more preferably less than 10 mass ppb, even more preferably 1 mass ppb or less, even more preferably less than 1 mass ppb, and particularly preferably less than the lower limit of quantification. The lower limit is not particularly limited, and may be an amount less than the lower limit of quantification.

[0097] The amount of the fluorine-containing compound having a molecular weight of 1,000 or less is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The resulting extract is concentrated using nitrogen purging as appropriate, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Prepare aqueous solutions with five or more levels of content of the standard substance, perform LC / MS analysis of the aqueous solutions with each content, plot the relationship between the content and the area for that content, and draw a calibration curve. Using the above calibration curve, the area of ​​the LC / MS chromatogram of the fluorine-containing compounds in the extract is converted to the content of the fluorine-containing compounds. The lower limit of quantification in this measurement method is 10 ppb by mass.

[0098] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include a fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 g / mol or less. The molecular weight of the fluorine-containing compound is preferably 800 or less, and more preferably 500 or less. Polymer particles obtained by polymerization in the presence of a fluorine-containing surfactant usually contain a fluorine-containing surfactant in addition to PTFE. In this specification, the fluorine-containing surfactant is one that is used during polymerization. The above-mentioned fluorine-containing compound having a molecular weight of 1000 or less may be a compound that is not added during polymerization, for example, a compound that is generated as a by-product during polymerization. In addition, when the fluorine-containing compound having a molecular weight of 1000 or less contains an anionic moiety and a cationic moiety, it means a compound containing fluorine in which the molecular weight of the anionic moiety is 1000 or less. The fluorine-containing compound having a molecular weight of 1000 or less does not include PTFE.

[0099] The hydrophilic group may be, for example, -COOM, -SO2M, or -SO3M, where -COOM, -SO3M (in each formula, M is H, a metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R1 is H or an organic group.

[0100] As the fluorine-containing surfactant, a surfactant containing fluorine (anionic fluorine-containing surfactant) whose anionic moiety has a molecular weight of 1000 or less can also be used. The "anionic moiety" refers to the part of the fluorine-containing surfactant excluding the cation. For example, F(CF2) n1 In the case of COOM, "F(CF2) n1 The "COO" part. The anionic fluorine-containing surfactant may be a surfactant represented by the following general formula (N 0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 is H, Cl or F. n0 Y is a linear, branched or cyclic alkylene group having 3 to 20 carbon atoms, in which some or all of the H's are substituted with F, and the alkylene group may contain one or more ether bonds, and some of the H's may be substituted with Cl. 0 is an anionic group. Y 0 The anionic group may be -COOM, -SO2M, or -SO3M, and may be -COOM or -SO3M. M is H, a metal atom, or NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 1 is H or an organic group. The metal atom includes alkali metals (Group 1), alkaline earth metals (Group 2), etc., such as Na, K, or Li. R 1 As the 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be: M is H, a metal atom or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. Above Rf n0 may be one in which 50% or more of H is substituted with fluorine.

[0101] The above fluorine-containing surfactant may be one type of fluorine-containing surfactant, or a mixture containing two or more types of fluorine-containing surfactants.

[0102] Examples of the fluorine-containing surfactant include compounds represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF2)7COOM, F(CF2)5COOM, H(CF2)6COOM, H(CF2)7COOM, CF3O(CF2)3OCHFCF2COOM, C3F7OCF(CF3)CF2OCF(CF3)COOM, CF3CF2CF2OCF(CF3)COOM, CF3CF2OCF2CF2OCF2COOM, C2F5OCF(CF3)CF2OCF(CF3)COOM, CF3OCF(CF3)CF2OCF(CF3)COOM, CF2ClCF2CF2OCF(CF3)CF2OCF2COOM, CF2ClCF2CF2OCF2CF(CF3)OCF2COOM, CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM, CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM, and [ka] (In each formula, M is H, metal atom, NR 14. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent. 1 is H or an organic group. The PTFE of the present disclosure is preferably substantially free of any of the fluorine-containing compounds represented by the above formulas.

[0103] In each of the above formulas, M is H, a metal atom, or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. R 1 is H or C 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be:

[0104] When the PTFE of the present disclosure is substantially free of any of the fluorine-containing compounds represented by the above formulas, gas generation and deterioration of the electrochemical device properties can be further suppressed. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably 20 mass ppb or less, more preferably 15 mass ppb or less, even more preferably 10 mass ppb or less, even more preferably less than 10 mass ppb, even more preferably 1 mass ppb or less, even more preferably less than 1 mass ppb, and particularly preferably less than the lower limit of quantification. The lower limit is not particularly limited, and may be an amount less than the lower limit of quantification.

[0105] The PTFE of the present disclosure has the following general formula: [C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14, preferably an integer of 9 to 12; M+ represents a cation. It is also preferable that the composition is substantially free of a fluorine-containing compound represented by the following formula (I): whereby gas generation and deterioration of the electrochemical device properties can be further suppressed. In the above formula, the cation M + The M in the above is the same as M described above. "Substantially free of the fluorine-containing compound represented by the above formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably 20 mass ppb or less, more preferably 15 mass ppb or less, even more preferably 10 mass ppb or less, even more preferably less than 10 mass ppb, even more preferably 1 mass ppb or less, even more preferably less than 1 mass ppb, and particularly preferably less than the lower limit of quantification. The lower limit is not particularly limited, and may be an amount less than the lower limit of quantification.

[0106] The PTFE of the present disclosure preferably has non-melt secondary processability. The non-melt secondary processability means a property that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, a property that does not flow easily even in the melting temperature range.

[0107] The PTFE of the present disclosure is less likely to become fibrous during transportation and is easier to feed, so that the standard specific gravity (SSG) is preferably 2.230 or less, more preferably 2.200 or less, even more preferably 2.180 or less, even more preferably 2.170 or less, even more preferably 2.165 or less, and particularly preferably 2.160 or less, and is preferably 2.130 or more, more preferably 2.135 or more, even more preferably 2.140 or more, even more preferably 2.145 or more, and particularly preferably 2.150 or more. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895 89.

[0108] The PTFE of the present disclosure is preferably non-paste extrudable, since it is less likely to fibrillate during transportation and is easier to feed. Whether or not PTFE can be paste-extruded is determined by the following method. 60 g of PTFE and 12.3 g of hydrocarbon oil (trade name: Isopar G (registered trademark), ExxonMobil) as an extrusion aid are mixed in a polyethylene container for 3 minutes. The above mixture is filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 0.47 MPa is applied to the piston inserted into the cylinder and held for 1 minute. Next, the mixture is extruded from the orifice at a ram speed of 20 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice is 100. If the bead breaks and cannot be extruded continuously, it is judged as not extrudable, and if the bead does not break and can be extruded continuously, it is judged as extrudable.

[0109] The form of the PTFE of the present disclosure is not limited, but is preferably a powder since it can be mixed with the electrode active material and solid electrolyte without using a large amount of dispersion medium. The PTFE may be in a form other than a powder, for example, a dispersion liquid.

[0110] The PTFE of the present disclosure may have an average secondary particle size of 350 μm or more, preferably 400 μm or more, and more preferably 450 μm or more, and is preferably 1000 μm or less, more preferably 900 μm or less, even more preferably 800 μm or less, even more preferably 700 μm or less, and particularly preferably 600 μm or less. The average secondary particle size is measured in accordance with JIS K 6891.

[0111] The PTFE of the present disclosure can be produced, for example, by suspension polymerization.

[0112] Suspension polymerization can be carried out, for example, by charging a monomer such as TFE, an aqueous medium, and other additives as necessary into a reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of a polymerization initiator to start the polymerization reaction. After the start of the polymerization reaction, a monomer such as TFE, a polymerization initiator, a chain transfer agent, and the like may be additionally added depending on the purpose.

[0113] Suspension polymerization can be carried out in the presence of a polymerization initiator. The polymerization initiator is not particularly limited as long as it can generate radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent or the like to initiate polymerization as a redox. The concentration of the polymerization initiator is appropriately determined depending on the type of monomer, the molecular weight of the desired polytetrafluoroethylene, and the reaction rate.

[0114] As the polymerization initiator, a water-soluble radical polymerization initiator can be used.

[0115] Examples of the water-soluble radical polymerization initiator include ionic radical initiators such as persulfates, such as ammonium persulfate, potassium persulfate, and alkali metal persulfates, and permanganates. In addition, these radical polymerization initiators may be used as an oxidizing component, and may be combined with, for example, hydrazine, diimine, iron(II) sulfate, copper(II) sulfate, oxalates, sulfites, or the like as a reducing component to form an oxidation-reduction initiator. Compounds capable of forming hydrates, such as iron(II) sulfate and copper(II) sulfate, may be anhydrides or hydrates.

[0116] Examples of the redox initiator include ammonium persulfate / copper(II) sulfate, ammonium persulfate / iron(II) sulfate, ammonium persulfate / sodium sulfite / iron(II) sulfate, ammonium persulfate / azodicarbonamide / copper(II) sulfate, ammonium persulfate / sodium azodicarboxylate / copper(II) sulfate, ammonium carbamate / copper(II) sulfate, ammonium persulfate / ammonium carbamate / copper(II) sulfate, and potassium permanganate / ammonium oxalate.

[0117] In the case of such a combination of redox initiators, it is preferable to charge one of them in advance into a polymerization vessel, and then add the other intermittently or continuously while carrying out the polymerization.

[0118] The amount of the radical polymerization initiator used is adjusted so as to allow good control of the reaction rate. For example, in the case of ammonium persulfate, the amount is preferably 1 to 100 ppm, more preferably 1 to 50 ppm, and most preferably 1 to 10 ppm, relative to the aqueous medium.

[0119] Suspension polymerization is carried out by polymerizing TFE in an aqueous medium under stirring. The aqueous medium means a liquid containing water. The aqueous medium is not particularly limited as long as it contains water.

[0120] The suspension polymerization can be carried out in the presence or absence of a surfactant. The amount of the surfactant is preferably 2000 mass ppm or less, more preferably 1000 mass ppm or less, even more preferably 500 mass ppm or less, even more preferably 200 mass ppm or less, even more preferably 100 mass ppm or less, and even more preferably 50 mass ppm or less, based on the aqueous medium. The amount of the surfactant may be 0 mass ppm, 0.5 mass ppm or more, 1 mass ppm or more, 5 mass ppm or more, or 10 mass ppm or more.

[0121] The surfactant used in the suspension polymerization is preferably a fluorine-containing surfactant. Examples of the fluorine-containing surfactant include an anionic fluorine-containing surfactant. The anionic fluorine-containing surfactant may be, for example, a surfactant containing fluorine atoms whose total carbon number excluding the anionic group is 20 or less.

[0122] As the fluorine-containing surfactant, a surfactant containing fluorine, the molecular weight of the anionic part of which is 1000 or less, preferably 800 or less, can be used. The "anionic part" refers to the part of the fluorine-containing surfactant excluding the cation. For example, F(CF2) represented by the formula (I) described below n1 In the case of COOM, "F(CF2) n1 The "COO" part.

[0123] The above-mentioned fluorine-containing surfactant also includes a fluorine-containing surfactant having a LogPOW of 3.5 or less. The LogPOW of the fluorine-containing surfactant is preferably 3.4 or less. The above-mentioned LogPOW is a partition coefficient between 1-octanol and water, and is represented by LogP [wherein P represents the ratio of the fluorine-containing surfactant concentration in octanol to the fluorine-containing surfactant concentration in water when a 1:1 octanol / water mixture containing the fluorine-containing surfactant undergoes phase separation].

[0124] The LogPOW is calculated from the HPLC elution time of the sample solution using a calibration curve of each elution time and the known octanol / water partition coefficient, which is prepared by performing HPLC on standard substances (heptanoic acid, octanoic acid, nonanoic acid, and decanoic acid) having known octanol / water partition coefficients under the following conditions: column: TOSOH ODS-120T column (φ4.6 mm×250 mm, manufactured by Tosoh Corporation), eluent: acetonitrile / 0.6% by mass HClO4 water=1 / 1 (vol / vol%), flow rate: 1.0 ml / min, sample amount: 300 μL, column temperature: 40° C., and detection light: UV 210 nm.

[0125] Specific examples of the fluorine-containing surfactant include those described in U.S. Patent Application Publication No. 2007 / 0015864, U.S. Patent Application Publication No. 2007 / 0015865, U.S. Patent Application Publication No. 2007 / 0015866, U.S. Patent Application Publication No. 2007 / 0276103, U.S. Patent Application Publication No. 2007 / 0117914, U.S. Patent Application Publication No. 2007 / 142541, U.S. Patent Application Publication No. 2008 / 0015319, U.S. Patent No. 3,250,808, and the like. No. 3,271,341, JP 2003-119204 A, WO 2005 / 042593 A, WO 2008 / 060461 A, WO 2007 / 046377 A, JP 2007-119526 A, WO 2007 / 046482 A, WO 2007 / 046345 A, U.S. Patent Application Publication No. 2014 / 0228531 A, WO 2013 / 189824 A, and WO 2013 / 189826 A can be mentioned.

[0126] The anionic fluorine-containing surfactant may be a surfactant represented by the following general formula (N 0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 is H, Cl or F. n0 Y is a linear, branched or cyclic alkylene group having 3 to 20 carbon atoms, in which some or all of the H's are substituted with F, and the alkylene group may contain one or more ether bonds, and some of the H's may be substituted with Cl. 0 is an anionic group. Y 0 The anionic group may be -COOM, -SO2M, or -SO3M, and may be -COOM or -SO3M. M is H, a metal atom, or NR 7 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 7is H or an organic group. The metal atom includes alkali metals (Group 1), alkaline earth metals (Group 2), etc., such as Na, K, or Li. R 7 As the 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be: M is H, a metal atom or NR 7 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 7 4, which may be H, Na, K, Li or NH4. Above Rf n0 may be one in which 50% or more of H is substituted with fluorine.

[0127] The above general formula (N 0 The compound represented by the following general formula (N 1 ): X n0 -(CF2) m1 -Y 0 (N 1 ) (In the formula, X n0 is H, Cl, or F; m1 is an integer of 3 to 15; Y 0 is as defined above, a compound represented by the following general formula (N 2 ): Rf n1 -O-(CF(CF3)CF2O) m2 CFX n1 -Y 0 (N 2 ) (In the formula, Rf n1 is a perfluoroalkyl group having 1 to 5 carbon atoms, m2 is an integer of 0 to 3, and X n1 is F or CF3, and Y 0 is as defined above, a compound represented by the following general formula (N 3 ): Rf n2 (CH2) m3 -(Rf n3 )q -Y 0 (N 3 ) (In the formula, Rf n2 is a partially or fully fluorinated alkyl group having 1 to 13 carbon atoms, which may contain an ether bond and / or a chlorine atom, m3 is an integer of 1 to 3, Rf n3 is a linear or branched perfluoroalkylene group having 1 to 3 carbon atoms, q is 0 or 1, and Y 0 is as defined above, a compound represented by the following general formula (N 4 ): Rf n4 -O-(CY n1 Y n2 ) p CF2-Y 0 (N 4 ) (In the formula, Rf n4 is a linear or branched, partially or completely fluorinated alkyl group having 1 to 12 carbon atoms, which may contain an ether bond; Y n1 and Y n2 are the same or different and are H or F, p is 0 or 1, and Y 0 is as defined above.) and a compound represented by the general formula (N 5 ): [ka] (In the formula, X n2 , X n3 and X n4 Rf may be the same or different and are H, F, or a linear or branched partially or completely fluorinated alkyl group having 1 to 6 carbon atoms, which may contain an ether bond. n5 is a linear or branched, partially or completely fluorinated alkylene group having 1 to 3 carbon atoms which may contain an ether bond; L is a linking group; Y 0 is as defined above, where X n2 , X n3 , X n4 and Rf n5 The total number of carbon atoms is 18 or less.

[0128] The above general formula (N 0 More specifically, the compound represented by the formula (I) is a perfluorocarboxylic acid (I), a ω-H perfluorocarboxylic acid (II), a perfluoroether carboxylic acid (III), a perfluoroalkyl alkylene carboxylic acid (IV), a perfluoroalkoxy fluorocarboxylic acid (V), a perfluoroalkyl sulfonic acid (VI), a ω-H perfluoro sulfonic acid (VII), a perfluoroalkyl alkylene sulfonic acid (VIII), a perfluoroalkyl alkylene sulfonic acid (IX), a fluorocarboxylic acid (X), a fluorocarboxylic acid (X), a alkoxy fluoro sulfonic acid (XI), a compound (XII), a compound (XIII), and the like.

[0129] The perfluorocarboxylic acid (I) is represented by the following general formula (I): F(CF2) n1 COOM (I) (In the formula, n1 is an integer of 3 to 14, and M is H, a metal atom, or NR 7 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 7 is H or an organic group.

[0130] The ω-H perfluorocarboxylic acid (II) is represented by the following general formula (II): H(CF2) n2 COOM (II) (wherein n2 is an integer of 4 to 15, and M is as defined above).

[0131] The perfluoroether carboxylic acid (III) is represented by the following general formula (III): Rf 1 -O-(CF(CF3)CF2O) n3 CF(CF3)COOM (III) (In the formula, Rf 1 is a perfluoroalkyl group having 1 to 5 carbon atoms, n3 is an integer of 0 to 3, and M is as defined above.

[0132] The perfluoroalkyl alkylene carboxylic acid (IV) is represented by the following general formula (IV): Rf 2 (CH2) n4 Rf 3 COOM (IV) (In the formula, Rf 2 is a perfluoroalkyl group having 1 to 5 carbon atoms, and Rf 3 is a linear or branched perfluoroalkylene group having 1 to 3 carbon atoms, n4 is an integer of 1 to 3, and M is as defined above.

[0133] The alkoxyfluorocarboxylic acid (V) is represented by the following general formula (V): Rf 4 -O-CY 1 Y 2 CF2-COOM (V) (In the formula, Rf 4 is a linear or branched partially or fully fluorinated alkyl group having 1 to 12 carbon atoms, which may contain an ether bond and / or a chlorine atom; Y 1 and Y 2 are the same or different and are H or F, and M is as defined above.

[0134] The perfluoroalkylsulfonic acid (VI) is represented by the following general formula (VI): F(CF2) n5 SO3M (VI) (wherein n5 is an integer of 3 to 14, and M is as defined above).

[0135] The above ω-H perfluorosulfonic acid (VII) is represented by the following general formula (VII): H(CF2) n6 SO3M (VII) (wherein n6 is an integer of 4 to 14, and M is as defined above).

[0136] The perfluoroalkyl alkylene sulfonic acid (VIII) is represented by the following general formula (VIII): Rf 5 (CH2) n7 SO3M (VIII) (In the formula, Rf 5 is a perfluoroalkyl group having 1 to 13 carbon atoms, n7 is an integer of 1 to 3, and M is as defined above.

[0137] The alkyl alkylene carboxylic acid (IX) is represented by the following general formula (IX): Rf 6 (CH2) n8 COOM (IX) (In the formula, Rf 6 is a linear or branched partially or fully fluorinated alkyl group having 1 to 13 carbon atoms which may contain an ether bond, n8 is an integer of 1 to 3, and M is as defined above.

[0138] The fluorocarboxylic acid (X) is represented by the following general formula (X): Rf 7 -O-Rf 8 -O-CF2-COOM (X) (In the formula, Rf 7 is a linear or branched, partially or completely fluorinated alkyl group having 1 to 6 carbon atoms, which may contain an ether bond and / or a chlorine atom; Rf 8 is a linear or branched, partially or fully fluorinated alkyl group having 1 to 6 carbon atoms, and M is as defined above.

[0139] The alkoxyfluorosulfonic acid (XI) is represented by the following general formula (XI): Rf 9 -O-CY 1 Y 2 CF2-SO3M (XI) (In the formula, Rf 9 is a linear or branched alkyl group having 1 to 12 carbon atoms, which may contain an ether bond, and which may contain chlorine, and which is partially or completely fluorinated; Y 1 and Y 2 are the same or different and are H or F, and M is as defined above.

[0140] The compound (XII) is represented by the following general formula (XII): [ka] (In the formula, X 1 , X 2 and X 3 Rf may be the same or different and are H, F, and linear or branched partially or completely fluorinated alkyl groups having 1 to 6 carbon atoms, which may contain an ether bond; 10 is a perfluoroalkylene group having 1 to 3 carbon atoms, L is a linking group, and Y 0 is an anionic group. Y 0 may be -COOM, -SO2M, or -SO3M, or may be -SO3M or COOM, where M is as defined above. Examples of L include a single bond and a partially or completely fluorinated alkylene group having 1 to 10 carbon atoms which may contain an ether bond.

[0141] The compound (XIII) is represented by the following general formula (XIII): Rf 11 -O-(CF2CF(CF3)O) n9 (CF2O) n10 CF2COOM (XIII) (In the formula, Rf 11is a fluoroalkyl group containing chlorine and having 1 to 5 carbon atoms, n9 is an integer of 0 to 3, n10 is an integer of 0 to 3, and M is as defined above.) Compound (XIII) is represented by CF2ClO(CF2CF(CF3)O) n9 (CF2O) n10 CF2COONH4 (a mixture having an average molecular weight of 750, where n9 and n10 are defined above).

[0142] As such, examples of the anionic fluorine-containing surfactant include carboxylic acid surfactants and sulfonic acid surfactants.

[0143] The fluorine-containing surfactant may be one type of fluorine-containing surfactant or a mixture containing two or more types of fluorine-containing surfactants.

[0144] The fluorine-containing surfactant may be a compound represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF2)7COOM, F(CF2)5COOM, H(CF2)6COOM, H(CF2)7COOM, CF3O(CF2)3OCHFCF2COOM, C3F7OCF(CF3)CF2OCF(CF3)COOM, CF3CF2CF2OCF(CF3)COOM, CF3CF2OCF2CF2OCF2COOM, C2F5OCF(CF3)CF2OCF(CF3)COOM, CF3OCF(CF3)CF2OCF(CF3)COOM, CF2ClCF2CF2OCF(CF3)CF2OCF2COOM, CF2ClCF2CF2OCF2CF(CF3)OCF2COOM, CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM, CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM, [ka] (In each formula, M is H, metal atom, NR 7 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent. 7 is H or an organic group.

[0145] The suspension polymerization particles obtained by suspension polymerization in the presence of fluorine-containing surfactant usually contain fluorine-containing surfactant in addition to polytetrafluoroethylene.In addition, the suspension polymerization particles obtained by polymerizing monomers such as TFE and modified monomers may contain fluorine-containing compounds generated by polymerization of monomers in addition to polytetrafluoroethylene.In the present disclosure, the fluorine-containing compound is a compound that is not added during suspension polymerization, and includes, for example, a compound that has a structure similar to that of a fluorine-containing surfactant but has a different carbon number.

[0146] According to the above-mentioned production method, polytetrafluoroethylene particles having a reduced content of fluorine-containing compounds produced by polymerization of monomers can be produced. Also, according to the production method of the present disclosure, even when suspension polymerization is carried out in the presence of a fluorine-containing surfactant, polytetrafluoroethylene particles having a reduced content of the fluorine-containing surfactant can be produced.

[0147] A typical compound as the fluorine-containing compound in the suspension polymerized particles is a fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 or less, preferably 800 g / mol or less. According to the above-mentioned production method, it is possible to produce polytetrafluoroethylene particles in which the content of the fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 or less, preferably 800 g / mol or less, in the suspension polymerized particles obtained by polymerization of a monomer such as TFE is reduced.

[0148] The hydrophilic group of the fluorine-containing compound is preferably an anionic group such as an acid group, and examples thereof include -NH2, -PO3M, -OPO3M, -SO3M, -OSO3M, and -COOM (in each formula, M represents a cation). Of these, -SO3M or -COOM is preferred as the hydrophilic group, and -COOM is more preferred.

[0149] In one embodiment of the suspension polymerized particles, the particles contain a compound represented by the following general formula (1) as a fluorine-containing compound having a hydrophilic group. General formula (1): [X-Rf-A - ] i M i+ (Wherein, X is H, Cl, Br, F or I; Rf is a linear or branched partially or fully fluorinated aliphatic group or a linear or branched partially or fully fluorinated aliphatic group interrupted by at least one oxygen atom; A - is the acid group, M i+ represents a cation having a valence i, where i is an integer from 1 to 3.

[0150] In one embodiment of the suspension polymerized particles, the particles contain a compound represented by the following general formula (2) as a fluorine-containing compound having a hydrophilic group. General formula (2):[C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14; M + represents a cation.)

[0151] It is known that the compound represented by general formula (2) (perfluoroalkanoic acid) is formed during polymerization when perfluoroalkyl vinyl ether or the like is used as a modified monomer (see WO 2019 / 161153).

[0152] In one embodiment of the suspension polymerized particles, the particles contain a compound represented by the following general formula (3) as a fluorine-containing compound having a hydrophilic group. General formula (3):[R 1-OL-CO2 - ]M + (In the formula, R 1 represents a linear or branched partially or fully fluorinated aliphatic group, or a linear or branched partially or fully fluorinated aliphatic group interrupted by at least one oxygen atom; L represents a linear or branched non-fluorinated, partially fluorinated or fully fluorinated alkylene group; M + represents a cation.)

[0153] In one embodiment of the suspension polymerized particles, the particles contain a compound represented by general formula (4) as the fluorine-containing compound having a hydrophilic group. General formula (4):[H-(CF2) m CO2 - ]M + (In the formula, m is an integer of 3 to 19, M + represents a cation.)

[0154] The suspension-polymerized particles thus obtained may be washed and then pulverized, or the suspension-polymerized particles thus obtained may be pulverized while being washed, to prepare pulverized particles.

[0155] The suspension polymerization particles obtained by suspension polymerization are usually obtained in a wet state. In the production method of the present disclosure, the suspension polymerization particles in a wet state may be pulverized, or the suspension polymerization particles in a wet state may be dried and then pulverized. The pulverization may be a wet pulverization or a dry pulverization.

[0156] The method of pulverizing the suspension polymerized particles includes, for example, a method of pulverizing using a pulverizer. Examples of the pulverizer include impact pulverizers such as a hammer mill, a pin mill, a high-speed rotary mill, and a jet mill, and friction pulverizers such as a cutter mill, a feather mill, and a colloid mill that pulverize by shearing force generated by a rotary blade and an outer stator (fixed blade). For pulverization, a combination of multiple pulverizers may be used.

[0157] The temperature at which the grinding treatment is carried out is preferably −200 to 50° C., more preferably 1° C. or higher, more preferably 40° C. or lower, and further preferably 30° C. or lower.

[0158] The method of pulverizing the suspension polymerized particles while washing them includes a method of pulverizing the suspension polymerized particles in water or an organic solvent. For example, water or an organic solvent and the suspension polymerized particles may be simultaneously supplied to a grinding type grinder such as a cutter mill to pulverize the suspension polymerized particles, or water or an organic solvent and the suspension polymerized particles may be mixed in advance, the mixture may be supplied to a grinder to pulverize the suspension polymerized particles.

[0159] Before the suspension-polymerized particles are pulverized, the suspension-polymerized particles may be washed. Water or an organic solvent may be used for washing the suspension-polymerized particles. The washing may be performed once or a plurality of times.

[0160] Examples of the organic solvent used for washing include ethers, halogenated hydrocarbons, aromatic hydrocarbons, pyridine, nitriles, nitrogen-containing polar organic compounds, dimethyl sulfoxide, and alcohols.

[0161] The pulverization may be carried out once, or may be carried out repeatedly until pulverized particles having a desired average particle size or a desired particle size distribution are produced.

[0162] The pulverized particles obtained by pulverization are usually obtained in a wet state. The moisture content of the pulverized particles after pulverization and before dehydration is, for example, more than 40% by mass. In the above-mentioned production method, the wet pulverized particles may be dehydrated. For example, a method of dehydrating the wet pulverized particles may be used. Examples of the dehydrator include a vibration dehydrator, a filtration dehydrator, and a centrifugal dehydrator. The dehydration is preferably performed at a temperature lower than 50°C. The dehydration temperature is the temperature of the atmosphere around the pulverized particles.

[0163] The wet pulverized particles may be dehydrated and further dried. Drying is performed for the purpose of removing moisture from the pulverized particles obtained by pulverization. For example, a method of drying the wet pulverized particles may be used, for example, a method of drying using a dryer.

[0164] Examples of the dryer include a hot air heat receiving type dryer, a conductive heat receiving type dryer, a radiation heat transfer type dryer, a high frequency heat transfer type dryer, etc. Examples of the dryer include a material stationary type dryer, a material transport type dryer, a material stirring type dryer, a material conveying type dryer, etc.

[0165] Examples of the hot air heat receiving type material stationary type dryer and material transport type dryer include a box type dryer, a tunnel dryer, a band dryer, a turbo vertical dryer, a vertical dryer, and a belt dryer. Examples of the hot air heat receiving type material agitation type dryer include a fluidized bed dryer, a ventilated rotary dryer, a groove type agitation dryer, and a multi-stage disk dryer. Examples of the hot air heat receiving type material conveying dryer include a flash dryer and a spray dryer (jet flow dryer, spray dryer).

[0166] Examples of conductive heat receiving type stationary material dryers and material transport type dryers include vacuum box type dryers, cylindrical dryers, vibration dryers, vacuum heat treatment dryers, freeze dryers, and drum dryers. Examples of the conductive heat receiving type material agitation dryer include a cylindrical dryer, a groove type dryer, an inverted cone type dryer, an extrusion dryer, and a steam heating tube bundle rotary dryer.

[0167] Examples of the radiation heat transfer type stationary material dryer and material transport type dryer include an infrared dryer and a superheated steam dryer.

[0168] Examples of the high-frequency heat transfer type stationary material dryer and material transport type dryer include a high-frequency dryer and a microwave dryer.

[0169] In one embodiment, the ground particles are dried by flash drying. Flash drying can be carried out using a flash dryer.

[0170] After drying the pulverized particles by flash drying, the solid-gas mixture containing the dried pulverized particles and gas may be separated into the pulverized particles and the gas using a cyclone or the like, and the pulverized particles may be recovered.

[0171] The temperature at which the pulverized particles are dried is preferably less than 300°C, more preferably less than 280°C, even more preferably less than 250°C, still more preferably less than 200°C, particularly preferably less than 180°C, most preferably less than 160°C, preferably not less than 50°C, more preferably not less than 100°C. The drying temperature is the temperature of the atmosphere around the pulverized particles, and when hot air is used for drying, it can be specified by measuring the temperature of the hot air. The temperature of the hot air can be measured at the supply port that supplies hot air to the dryer or the exhaust port that exhausts hot air from the dryer, but is preferably measured at the exhaust port.

[0172] The water content of the pulverized particles is preferably 40% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.010 or less, even more preferably 0.005 or less, even more preferably 0.003 or less, even more preferably 0.002 or less, and particularly preferably 0.001 or less. The water content of the pulverized particles can be adjusted, for example, by dehydrating or drying the pulverized particles. The water content of the pulverized particles can be calculated, for example, by heating the pulverized particles at 150 ° C. for 2 hours to thoroughly dry them, measuring the mass of the pulverized particles before and after heating, and according to the following formula. Moisture content (mass%) = [(mass of ground particles before heating (g)) - (mass of ground particles after heating (g))] / (mass of ground particles after heating (g)) x 100

[0173] After the suspension polymerized particles are pulverized, the pulverized particles obtained may be classified by a known method such as air classification, etc. By classifying, fine particles having a very small particle size and coarse particles having a very large particle size can be removed to obtain pulverized particles having a desired average particle size or a desired particle size distribution.

[0174] The average particle size of the pulverized particles is preferably 800 μm or less, more preferably 600 μm or less, even more preferably 400 μm or less, preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, still more preferably 100 μm or more, particularly preferably 150 μm or more, and most preferably more than 200 μm. As described above, the pulverized particles often have a torn shape or a large flat shape due to the pulverization process. Usually, they often have a scaly particle shape. In this specification, "PTFE particles having a particle diameter of 1 μm or more" refers to the scaly particles.

[0175] The resulting pulverized particles may be granulated by a known granulation method.

[0176] The PTFE of the present disclosure can also be produced by mixing PTFE obtained by emulsion polymerization with PTFE obtained by suspension polymerization. The mixing method is not limited, and all of the PTFE may be mixed in the form of powder, or the PTFE may be mixed in the form of an aqueous dispersion and the powder.

[0177] The PTFE of the present disclosure can be suitably produced, for example, by a production method including a step (A) of mixing an aqueous dispersion of PTFE obtained by emulsion polymerization with a powder of PTFE obtained by suspension polymerization, a step (B) of coagulating the aqueous dispersion after mixing to obtain a wet powder, and a step (C) of drying the wet powder.

[0178] The aqueous dispersion in step (A) can be produced by emulsion polymerization.

[0179] The emulsion polymerization can be carried out by a known method. For example, in the presence of an anionic fluorine-containing surfactant and a polymerization initiator, the emulsion polymerization of monomers (TFE and optionally modified monomers) required for forming the PTFE can be carried out in an aqueous medium to obtain an aqueous dispersion containing the PTFE particles (primary particles). In the emulsion polymerization, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, etc. may be used as necessary.

[0180] The aqueous dispersion may contain at least one of the above-mentioned fluorine-containing compounds.

[0181] The above emulsion polymerization can be carried out, for example, in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator. The emulsion polymerization can be carried out by charging an aqueous medium, the anionic fluorine-containing surfactant, monomers and, if necessary, other additives into a polymerization reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of polymerization initiator to initiate the polymerization reaction. After the start of the polymerization reaction, monomers, polymerization initiators, chain transfer agents, the surfactants and the like may be additionally added depending on the purpose.

[0182] The polymerization initiator is not particularly limited as long as it can generate radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent or the like to initiate polymerization as a redox. The concentration of the polymerization initiator is appropriately determined depending on the type of monomer, the molecular weight of the desired PTFE, and the reaction rate.

[0183] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0184] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluorovaleryl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro Representative examples include di[perfluoro(or fluorochloro)acyl]peroxides such as di(ω-hexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.

[0185] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, sodium salts, t-butyl permaleate, t-butyl hydroperoxide, disuccinic acid peroxide, etc., of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc. Among these, ammonium persulfate and disuccinic acid peroxide are preferred. A reducing agent such as sulfites and sulfites may also be included, and the amount used may be 0.1 to 20 times that of the peroxide.

[0186] The amount of the water-soluble radical polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (e.g., several ppm relative to water concentration) at least to the extent that the polymerization rate does not decrease significantly. The upper limit is a range in which the reaction temperature may be increased while removing heat from the equipment side by the polymerization reaction heat, and a more preferable upper limit is a range in which the polymerization reaction heat can be removed from the equipment side. In terms of easily obtaining the above-mentioned physical properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.

[0187] For example, when polymerization is carried out at a low temperature of 30° C. or less, it is preferable to use a redox initiator that combines an oxidizing agent and a reducing agent as the polymerization initiator. Examples of the oxidizing agent include persulfates, organic peroxides, potassium permanganate, manganese triacetate, cerium ammonium nitrate, and bromates. Examples of the reducing agent include sulfites, bisulfites, bromates, diimines, and oxalic acid. Examples of the persulfates include ammonium persulfate and potassium persulfate. Examples of the sulfites include sodium sulfite and ammonium sulfite. In order to increase the decomposition rate of the initiator, it is also preferable to add a copper salt or an iron salt to the combination of the redox initiator. Examples of the copper salt include copper(II) sulfate, and examples of the iron salt include iron(II) sulfate.

[0188] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, a persulfate, manganese triacetate, a cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof, or a diimine. More preferably, the oxidizing agent is permanganic acid or a salt thereof, a persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.

[0189] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate. When a redox initiator is used, either the oxidizing agent or the reducing agent may be charged in advance in a polymerization tank, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / oxalic acid is used, it is preferable to charge oxalic acid in a polymerization tank and continuously add potassium permanganate thereto. In this specification, when the redox initiator is described as "potassium permanganate / oxalic acid," it means a combination of potassium permanganate and oxalic acid. The same applies to other compounds.

[0190] The redox initiator is particularly preferably a combination of an oxidizing agent that is a salt and a reducing agent that is a salt. For example, the oxidizing agent which is the salt is more preferably at least one selected from the group consisting of persulfates, permanganates, cerium (IV) salts, and bromates, further preferably permanganates, and particularly preferably potassium permanganate. The reducing agent which is the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.

[0191] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate, and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, and cerium ammonium nitrate / ammonium oxalate, and even more preferably potassium permanganate / oxalic acid.

[0192] When a redox initiator is used, the oxidizing agent and the reducing agent may be added all at once at the beginning of the polymerization, the reducing agent may be added all at once at the beginning of the polymerization and the oxidizing agent may be added continuously, the oxidizing agent may be added all at once at the beginning of the polymerization and the reducing agent may be added continuously, or both the oxidizing agent and the reducing agent may be added continuously.

[0193] When one of the above redox polymerization initiators is added at the beginning of the polymerization and the other is added continuously, it is preferable to gradually reduce the rate of addition in order to obtain PTFE with a low SSG, and it is further preferable to stop the addition midway through the polymerization, and the timing for stopping the addition is preferably before 20 to 40 mass % of the total TFE consumed in the polymerization reaction is consumed.

[0194] When using a redox initiator as a polymerization initiator, the amount of oxidizing agent added to the aqueous medium is preferably 0.1 ppm or more, more preferably 0.3 ppm or more, more preferably 0.5 ppm or more, even more preferably 1 ppm or more, particularly preferably 5 ppm or more, and particularly preferably 10 ppm or more, and also preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 50 ppm or less. The amount of reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, more preferably 3 ppm or more, more preferably 5 ppm or more, particularly preferably 10 ppm or more, and also preferably 10000 ppm or less, more preferably 1000 ppm or less, more preferably 100 ppm or less, and even more preferably 50 ppm or less. When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100° C. or lower, more preferably 95° C. or lower, and even more preferably 90° C. or lower. The polymerization temperature is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.

[0195] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred in that the above-mentioned properties can be easily obtained.

[0196] The aqueous medium is a reaction medium for polymerization, and refers to a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and, for example, a fluorine-free organic solvent such as an alcohol, ether, or ketone, and / or a fluorine-containing organic solvent having a boiling point of 40° C. or less.

[0197] In the above emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposer for the polymerization initiator, a dicarboxylic acid, and the like may be used, if necessary.

[0198] The emulsion polymerization is preferably carried out with the addition of a nucleating agent for the purpose of adjusting the particle size. The nucleating agent is preferably added before the start of the polymerization reaction. As the nucleating agent, a known agent can be used. For example, it is preferable that the nucleating agent is at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents, and it is more preferable that the nucleating agent is a nonionic surfactant.

[0199] The fluoropolyether may, for example, be a perfluoropolyether (PFPE) acid or a salt thereof. The perfluoropolyether (PFPE) acid or salt thereof may have any chain structure in which oxygen atoms in the backbone of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. Also, two or more types of fluorocarbon groups may be present in the molecule. A representative structure has a repeating unit represented by the following formula: (-CFCF3-CF2-O-) n (-CF2-CF2-CF2-O-) n (-CF2-CF2-O-) n -(-CF2-O-) m (-CF2-CFCF3-O-) n -(-CF2-O-) m

[0200] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed therein, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. The PFPE acid or its salt may also have a sulfonic acid, phosphonic acid group or their salt at one or both ends. The PFPE acid or its salt may also have a different group at each end. For monofunctional PFPEs, the other end of the molecule is usually perfluorinated, but may contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least two ether oxygens, preferably at least four ether oxygens, and even more preferably at least six ether oxygens. Preferably, at least one of the fluorocarbon groups separating the ether oxygens, more preferably at least two of such fluorocarbon groups, has two or three carbon atoms. Even more preferably, at least 50% of the fluorocarbon groups separating the ether oxygens have 2 or 3 carbon atoms. Also preferably, the PFPE acid or salt thereof has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure above is at least 5. Two or more of the PFPE acids or salts thereof having an acid group at one or both termini may be used in the manufacturing method of the present disclosure. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.

[0201] The emulsion polymerization is preferably carried out by adding a radical scavenger or a decomposer of the polymerization initiator, since it can further increase the molecular weight of PTFE and improve the strength of the composite sheet.The radical scavenger or the decomposer of the polymerization initiator is preferably added after the start of the polymerization reaction, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and preferably before 50% by mass or less, preferably 40% by mass or less is polymerized.When depressurizing and repressurizing as described below are performed, it is preferable to add it after that.

[0202] The radical scavenger is a compound that does not have the ability to restart after addition or chain transfer to the free radical in the polymerization system. Specifically, a compound that easily undergoes a chain transfer reaction with a primary radical or a growing radical, and then generates a stable radical that does not react with a monomer, or a compound that easily undergoes an addition reaction with a primary radical or a growing radical, and generates a stable radical, is used. Generally, the activity of what is called a chain transfer agent is characterized by the chain transfer constant and the reinitiation efficiency, but among chain transfer agents, those with a reinitiation efficiency of almost 0% are called radical scavengers. The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero percent. "Reinitiation efficiency is substantially zero percent" means that the generated radicals turn the radical scavenger into stable radicals. Preferably, the compound has a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) of more than 0.1. The above compound has a chain transfer constant (Cs) of more preferably 0.5 or more, even more preferably 1.0 or more, even more preferably 5.0 or more, and particularly preferably 10 or more.

[0203] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl2). Examples of the aromatic hydroxy compound include unsubstituted phenol, polyhydric phenol, salicylic acid, m- or p-salicylic acid, gallic acid, and naphthol. The unsubstituted phenols include o-, m-, or p-nitrophenol, o-, m-, or p-aminophenol, p-nitrosophenol, etc. The polyhydric phenols include catechol, resorcinol, hydroquinone, pyrogallol, phloroglucinol, naphthresorcinol, etc. Examples of aromatic amines include o-, m- or p-phenylenediamine, benzidine, and the like. Examples of the quinone compound include o-, m- or p-benzoquinone, 1,4-naphthoquinone, alizarin, and the like. Examples of thiocyanates include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN). Of the above radical scavengers, aromatic hydroxy compounds are preferred, unsubstituted phenols or polyhydric phenols are more preferred, and hydroquinone is even more preferred.

[0204] The amount of the radical scavenger added is preferably an amount equivalent to 3 to 500% (molar basis) of the polymerization initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0205] The decomposer for the polymerization initiator may be any compound capable of decomposing the polymerization initiator used, and is preferably at least one selected from the group consisting of sulfites, bisulfites, bromates, diimines, diimine salts, oxalic acid, oxalates, copper salts, and iron salts. Examples of sulfites include sodium sulfite and ammonium sulfite. Examples of copper salts include copper(II) sulfate, and examples of iron salts include iron(II) sulfate. The amount of the decomposition agent added is preferably an amount equivalent to 3 to 500% (molar basis) of the initiator concentration from the viewpoint of appropriately reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).

[0206] The emulsion polymerization may be carried out in the presence of 5 to 500 ppm of dicarboxylic acid relative to the aqueous medium in order to reduce the amount of coagulation produced during polymerization, and is preferably carried out in the presence of 10 to 200 ppm of dicarboxylic acid. If the amount of dicarboxylic acid is too small relative to the aqueous medium, sufficient effects may not be obtained, and if the amount is too large, a chain transfer reaction may occur, resulting in a low molecular weight polymer. The amount of dicarboxylic acid is more preferably 150 ppm or less. The dicarboxylic acid may be added before the start of the polymerization reaction or during the polymerization.

[0207] The dicarboxylic acid is preferably, for example, one represented by the general formula: HOOCRCOOH (wherein R represents an alkylene group having 1 to 5 carbon atoms), more preferably succinic acid, malonic acid, glutaric acid, adipic acid, or pimelic acid, and even more preferably succinic acid.

[0208] In the above emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined depending on the type of monomer used, the molecular weight of the target PTFE, and the reaction rate. Usually, the polymerization temperature is 5 to 150°C, preferably 10°C or higher, more preferably 30°C or higher, and even more preferably 50°C or higher. Also, it is more preferably 120°C or lower, and even more preferably 100°C or lower. The polymerization pressure is 0.05 to 10 MPaG. The polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Also, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.

[0209] When VDF is used as the modified monomer, in the emulsion polymerization, the VDF concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in order to easily obtain the above-mentioned physical properties. The concentration may be 15 mol% or less, preferably 6.0 mol% or less, more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and particularly preferably 1.0 mol% or less. The VDF concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. It is preferable to charge VDF all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0210] When VDF is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after VDF is charged into the polymerization vessel until the polymerization is completed. This allows VDF to remain in the system until the end of the polymerization, and the strength of the resulting PTFE-based composite sheet can be further increased.

[0211] When HFP is used as the modified monomer, in the emulsion polymerization, the HFP concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.01 to 3.0 mol % in order to easily obtain the above-mentioned properties. Furthermore, the HFP concentration in the gas in the reactor at the time when 40 mass % of the total TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol % and 0.2 mol % or less. The above HFP concentration is preferably maintained until the end of the polymerization reaction. HFP may be charged all at once before the start of polymerization, or a portion may be charged before the start of polymerization and added continuously or intermittently after the start of polymerization. By allowing HFP to remain until the end of the polymerization reaction, the extrusion pressure is reduced even though the strength of the resulting mixture sheet using PTFE is high.

[0212] When HFP is used as the modifying monomer, in the above emulsion polymerization, it is preferable to release the pressure before 5 to 40 mass % of the total TFE consumed in the polymerization reaction is polymerized, and then re-pressurize using only TFE, in order to further improve the strength of the resulting composite sheet using PTFE. The pressure reduction is preferably carried out so that the pressure inside the reactor is 0.2 MPaG or less, more preferably 0.1 MPaG or less, and even more preferably 0.05 MPaG or less. Also, it is preferably carried out so that the pressure inside the reactor is 0.0 MPaG or more. The above pressure reduction and re-increase may be carried out several times. The pressure reduction may be carried out until the pressure is reduced using a vacuum pump.

[0213] When CTFE is used as the modified monomer, in the emulsion polymerization, the CTFE concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, in order to easily obtain the above-mentioned properties. The above concentration is also preferably 3.0 mol% or less, more preferably 1.0 mol% or less. The above CTFE concentration may be maintained until the end of the polymerization reaction, or depressurization may be performed during the reaction. CTFE is preferably charged all at once before the start of polymerization, but a portion of it may be added continuously or intermittently after the start of polymerization.

[0214] When CTFE is used as the modified monomer, it is preferable not to release the pressure in the emulsion polymerization after CTFE is charged into the polymerization vessel until the polymerization is completed. This allows CTFE to remain in the system until the end of the polymerization, and the strength of the resulting composite sheet using PTFE can be further increased.

[0215] The powder in step (A) can be produced by suspension polymerization, which is as described above.

[0216] The mixing in step (A) can be carried out by a known method.

[0217] The coagulation in step (B) can be carried out by a known method.

[0218] In step (C), the drying is usually carried out by using a vacuum, high frequency, hot air, or other means while keeping the wet powder in a state where it is not very fluidized, preferably in a stationary state. Friction between powders, especially at high temperatures, generally has an undesirable effect on fine powder-type PTFE. This is because particles made of this type of PTFE have the property of easily fibrillating even with a small shear force and losing the original stable particle structure.

[0219] In step (C), it is preferable to place the wet powder obtained in step (B) in a container having air permeability at the bottom and / or sides, and heat-treat for 2 hours or more at a temperature of 130 to 300° C. By carrying out heat-treating under such extremely limited conditions, the fluorine-containing compound having a molecular weight of 1000 or less can be efficiently removed together with water, and the contents of the fluorine-containing compound and water can be within the above-mentioned ranges.

[0220] The temperature of the heat treatment in step (C) is preferably 140°C or higher, more preferably 150°C or higher, even more preferably 160°C or higher, even more preferably 180°C or higher, even more preferably 200°C or higher, particularly preferably 220°C or higher, and is preferably 280°C or lower, more preferably 250°C or lower, in order to more efficiently remove moisture and fluorine-containing compounds.

[0221] The time for the heat treatment in step (C) is preferably 5 hours or more, more preferably 10 hours or more, and even more preferably 15 hours or more, in terms of more efficiently removing moisture and fluorine-containing compounds. The upper limit is not particularly limited, but is, for example, preferably 100 hours, more preferably 50 hours, and even more preferably 30 hours.

[0222] The wind speed in step (C) is preferably 0.01 m / s or more, more preferably 0.03 m / s or more, even more preferably 0.05 m / s or more, and even more preferably 0.1 m / s or more, from the viewpoint of more efficiently removing moisture and fluorine-containing compounds, and is preferably 50 m / s or less, more preferably 30 m / s or less, and even more preferably 10 m / s or less, from the viewpoint of suppressing scattering of powder.

[0223] The heat treatment in step (C) can be carried out using an electric furnace or a steam furnace. For example, it can be carried out using electric furnaces such as a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a radiant conveyor type electric furnace, a fluidized bed electric furnace, a vacuum electric furnace, an agitation type electric furnace, an airflow type electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace). In terms of being able to remove moisture and fluorine-containing compounds more efficiently, a parallel flow box type electric furnace, a ventilated box type electric furnace, a ventilated conveyor type electric furnace, a band electric furnace, a fluidized bed electric furnace, a hot air circulation type electric furnace, or a steam furnace corresponding to the above (a device in which the electric furnace in the device name of each electric furnace is replaced with a steam furnace) is preferred.

[0224] The heat treatment in step (C) is preferably carried out by placing the wet powder in a container whose bottom and / or sides are air permeable, in order to more efficiently remove moisture and fluorine-containing compounds. The container whose bottom and / or sides are air permeable may be any container that can withstand the heat treatment temperature, and is preferably made of a metal such as stainless steel. The container having breathable bottom and / or sides is preferably a tray (bat) having breathable bottom and / or sides, and more preferably a tray having a mesh bottom and / or sides (mesh tray). The mesh is preferably either a woven mesh or a punched metal. The mesh size is preferably 2000 μm or less (ASTM standard 10 mesh or more), more preferably 595 μm or less (30 mesh or more), even more preferably 297 μm or less (50 mesh or more), even more preferably 177 μm or less (80 mesh or more), particularly preferably 149 μm or less (100 mesh or more), and particularly preferably 74 μm or less (200 mesh or more). Also, 25 μm or more (500 mesh or less) is preferable. When the mesh is a woven net, the weaving method may be, for example, plain weave, twill weave, plain tatami weave, or twill tatami weave. When the mesh is a punched metal, the aperture ratio is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more, and is preferably 95% or less.

[0225] In the step (C), the amount of the moist powder is preferably 10 g / cm from the viewpoint of more efficiently removing moisture and fluorine-containing compounds. 2 It is preferable that the thickness is less than 8 g / cm 2 More preferably, it is 5 g / cm or less. 2 More preferably, it is 3 g / cm or less. 2 It is particularly preferable that the density is 0.01 g / cm or less. 2 It is preferable that the concentration is 0.05 g / cm or more. 2 More preferably, it is 0.1 g / cm or more. 2 More preferably, it is equal to or greater than this.

[0226] The moisture content of the moist powder to be heat-treated in step (C) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, relative to the moist powder, in order to more efficiently remove moisture and fluorine-containing compounds, and is preferably 150% by mass or less, and more preferably 100% by mass or less.

[0227] The PTFE of the present disclosure can also be suitably produced by a production method including a step (D) of mixing a PTFE powder obtained by emulsion polymerization with a PTFE powder obtained by suspension polymerization.

[0228] The PTFE powder obtained by emulsion polymerization in step (D) can be produced by coagulating the aqueous dispersion of PTFE obtained by emulsion polymerization, followed by drying. The aqueous dispersion can be produced by the same method as the aqueous dispersion of PTFE obtained by emulsion polymerization in step (A). The coagulation and drying can be carried out by the same method as steps (B) and (C).

[0229] The PTFE powder obtained by suspension polymerization in step (D) can be produced in the same manner as the PTFE powder obtained by suspension polymerization in step (A).

[0230] The mixing in step (D) can be carried out by a known dry mixing method.

[0231] The PTFE of the present disclosure is used in a binder for electrochemical devices. In the binder for electrochemical devices, the PTFE of the present disclosure may be used alone or may be mixed with other materials (e.g., polymers other than PTFE). However, it is preferable to use the PTFE of the present disclosure substantially alone, and it is more preferable to use it alone. Note that, "using the PTFE of the present disclosure substantially alone" means that the amount of PTFE in the binder for electrochemical devices is used within the range described below.

[0232] The present disclosure relates to a binder for electrochemical devices that is substantially composed of PTFE, the PTFE having a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 / g (hereinafter also referred to as binder (1) of the present disclosure).

[0233] The present disclosure relates to a binder for electrochemical devices that is substantially composed of PTFE, the PTFE having a specific surface area of ​​0.5 m 2 / g or more 7.0m 2The present invention also provides a binder for electrochemical devices containing 40 mass % or more of PTFE having a molecular weight of less than 1000 / g (hereinafter also referred to as binder (2) of the present disclosure).

[0234] The present disclosure also provides a binder for electrochemical devices consisting essentially of PTFE, the PTFE containing 40 mass% or more of PTFE obtained by suspension polymerization (hereinafter also referred to as binder (3) of the present disclosure).

[0235] The present disclosure also provides a binder for electrochemical devices consisting essentially of PTFE, in which the PTFE contains 40 mass % or more of PTFE including PTFE particles having a particle diameter of 1 μm or more (hereinafter also referred to as binder (4) of the present disclosure).

[0236] In this specification, unless otherwise specified, binders (1) to (4) of the present disclosure are collectively referred to as "binders of the present disclosure."

[0237] The binder of the present disclosure contains a specific PTFE, so that it is difficult to become fibrous during transportation and is easy to feed. In particular, when feeding using a feeder, clogging of the feeder (adhesion to the feeder) is unlikely to occur. Furthermore, it is possible to reduce the cleaning work of dismantling the feeder.

[0238] The binder of the present disclosure is also advantageous in terms of production process because it does not require the use of a large amount of a dispersion medium such as water or an organic solvent, and a wide range of electrode active materials and solid electrolytes can be selected for combination with the binder, and the process and cost involved in using a dispersion medium can be reduced. Furthermore, since the binder of the present disclosure has excellent binding strength with the active material and the electrolyte, the amount of the binder used can be reduced.

[0239] As the PTFE in the binder of the present disclosure, the same PTFE as that of the present disclosure described above can be used, and the preferred embodiments are also the same.

[0240] The binder of the present disclosure is substantially composed of the PTFE. This allows the effects of the PTFE to be significantly exhibited. "Substantially composed of the PTFE" means that the content of the PTFE is 95.0% by mass or more relative to the binder. The content of the PTFE relative to the binder is preferably 98.0% by mass or more, more preferably 99.0% by mass or more, even more preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more. It is also preferred that the binder of the present disclosure consists solely of the above-mentioned PTFE.

[0241] The binder of the present disclosure is preferably substantially free of organic solvent. This can reduce the steps and costs involved in using organic solvents. "Substantially free of organic solvent" means that the organic solvent content of the binder is 5% by mass or less. The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.

[0242] The binder of the present disclosure is preferably in the form of a powder.

[0243] The binders of the present disclosure are used in electrochemical devices such as batteries and capacitors. The battery may be a secondary battery such as a lithium ion battery. The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include an electric double layer capacitor, a hybrid capacitor, and a redox capacitor. Examples of the hybrid capacitor include a sodium ion capacitor, a lithium ion capacitor, and a magnesium ion capacitor. Among these, an electric double layer capacitor is particularly preferred.

[0244] The binder of the present disclosure can be suitably used as a binder for batteries, and can be particularly suitably used as a binder for secondary batteries such as lithium ion batteries. The binders of the present disclosure may be used to fabricate electrochemical device components, preferably battery components. The binder of the present disclosure can be particularly suitably used as a binder for electrodes. The binder of the present disclosure can also be suitably used as a binder in the solid electrolyte layer of a solid secondary battery.

[0245] The present disclosure also provides an electrode mixture containing the above-mentioned PTFE of the present disclosure or the binder of the present disclosure and an electrode active material. By using the electrode mixture of the present disclosure, the powder components of the electrochemical device are uniformly dispersed, and a mixture sheet having excellent strength and flexibility is obtained. In addition, even if the amount of binder is small, the electrode active material can be held, so that more materials that improve the electrochemical device properties, such as active materials and conductive assistants, can be added.

[0246] The electrode active material includes a positive electrode active material and a negative electrode active material.

[0247] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc. In a preferred embodiment, the alkali metal ion may be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.

[0248] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge) and alkali metal-cobalt composite oxides (lithium-cobalt composite oxides, etc.). In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0249] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co0.15 Al 0.05 O2 or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like are preferred, and a compound represented by the following general formula (3) is preferred. MNi h Co i Mn j M 5 k O2(3) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0250] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula (4): M e M 4 f (PO4) g (4) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li. That is, the alkali metal-containing transition metal phosphate compound is preferably a lithium-containing transition metal phosphate compound.

[0251] The transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound is preferably one having an olivine structure.

[0252] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula (5): Li y Ni 1-x M x O2(5) (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0253] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 A positive electrode active material such as O2 is preferable because the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or more. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the above-mentioned positive electrode active material is preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.

[0254] Other positive electrode active materials include M2MnO3 and MM6 O2 (where M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) and solid solution materials thereof can also be mentioned.

[0255] Examples of the solid solution material include, for example, the general formula Mx[Mn (1-y) M 7 y O z represented by an alkali metal manganese oxide. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and includes, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 A manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as Li2MnO3 is preferable because it can provide an alkali metal ion secondary battery having a high energy density.

[0256] In addition, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferable to mix and use the above positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably at least 0.1% by mass, more preferably at least 0.3% by mass, still more preferably at least 0.5% by mass, and preferably at most 10% by mass, more preferably at most 8% by mass, still more preferably at most 5% by mass, based on the total of the above positive electrode active material and lithium phosphate.

[0257] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0258] These surface-attaching substances can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending in a solvent, impregnating and adding to the positive electrode active material, and drying, a method of dissolving or suspending a surface-attaching substance precursor in a solvent, impregnating and adding to the positive electrode active material, and then reacting by heating, etc., a method of adding to a positive electrode active material precursor and simultaneously baking, etc. When carbon is attached, a method of mechanically attaching carbonaceous material in the form of, for example, activated carbon, etc., afterwards can also be used.

[0259] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more, and preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less, by mass relative to the positive electrode active material. The surface-attached substance can suppress the oxidation reaction of the electrolyte on the surface of the positive electrode active material and can improve the battery life, but if the amount of attachment is too small, the effect is not fully manifested, and if it is too large, the ingress and egress of lithium ions is inhibited, which may increase the resistance.

[0260] The shape of the particles of the positive electrode active material may be any of the conventional shapes such as block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles.

[0261] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3That is all. If the tap density of the positive electrode active material is below the lower limit, the amount of dispersion medium required during the formation of the positive electrode active material layer increases, and the amount of conductive material and binder required also increases, restricting the filling rate of the positive electrode active material in the positive electrode active material layer and possibly restricting the battery capacity. By using a composite oxide powder with a high tap density, a high density positive electrode active material layer can be formed. Generally, the higher the tap density, the better, and there is no particular upper limit, but if it is too high, the diffusion of lithium ions in the positive electrode active material layer using the electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated, so that the upper limit is preferably 4.0 g / cm. 3 Less than or equal to 3.7 g / cm 3 More preferably, 3.5 g / cm 3 The following is the result. The above tap density is the powder packing density (tap density) g / cm when 5 to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and tapped 200 times with a stroke of approximately 20 mm. 3 is required.

[0262] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when primary particles are aggregated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, and most preferably 1.0 μm or more, and is preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, and most preferably 22 μm or less. If it is below the lower limit, a high tap density product may not be obtained, and if it exceeds the upper limit, it may take time for lithium to diffuse within the particles, resulting in problems such as a decrease in battery performance. Here, by mixing two or more types of the above positive electrode active materials having different median diameters d50, the filling property during positive electrode production can be further improved.

[0263] The median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, the measurement is performed by using a 0.1% by mass aqueous solution of sodium hexametaphosphate as the dispersion medium, and setting the measurement refractive index to 1.24 after ultrasonic dispersion for 5 minutes.

[0264] In the case where the primary particles are aggregated to form secondary particles, the average primary particle diameter of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which may adversely affect the powder packing property or greatly reduce the specific surface area, and therefore the battery performance such as output characteristics may be likely to decrease. On the other hand, if the lower limit is exceeded, problems such as poor reversibility of charge and discharge may occur due to underdeveloped crystals. The average primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest intercept value of a horizontal line at the left and right boundaries of a primary particle is determined for any 50 primary particles, and the average value is calculated.

[0265] The BET specific surface area of ​​the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, whereas if it is larger, it becomes difficult to increase the tap density, and problems may easily occur in the processability when forming the positive electrode active material layer. The BET specific surface area is defined as a value measured by a nitrogen adsorption BET one-point method using a gas flow method, using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.) after pre-drying a sample at 150°C for 30 minutes under a nitrogen flow and then using a nitrogen / helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.

[0266] When the secondary battery of the present disclosure is used as a large-sized lithium-ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so it is preferable that the particles of the positive electrode active material are mainly secondary particles. The particles of the positive electrode active material preferably have an average secondary particle diameter of 40 μm or less and contain 0.5 to 7.0 volume % of fine particles having an average primary particle diameter of 1 μm or less. By containing fine particles having an average primary particle diameter of 1 μm or less, the contact area with the electrolyte is increased, and the diffusion of lithium ions between the electrode mixture and the electrolyte can be made faster, resulting in improved output performance of the battery.

[0267] The manufacturing method of the positive electrode active material is a general method for manufacturing inorganic compounds.In particular, various methods can be considered for manufacturing spherical or elliptical active materials, such as dissolving or pulverizing and dispersing the raw material of transition metal in a solvent such as water, adjusting the pH while stirring to produce and recover a spherical precursor, drying this as necessary, adding a Li source such as LiOH, Li2CO3, LiNO3, and baking at high temperature to obtain an active material.

[0268] For the production of the positive electrode, the positive electrode active material may be used alone, or two or more of different compositions may be used in any combination or ratio. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.

[0269] The content of the positive electrode active material is preferably 50 to 99.5% by mass of the positive electrode mixture, more preferably 80 to 99% by mass, in terms of high battery capacity. The content in the positive electrode active material layer is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. The upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the strength of the positive electrode may be insufficient.

[0270] The negative electrode active material is not particularly limited, and examples thereof include lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbonaceous materials such as non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li4Ti5O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0271] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0272] The silicon-containing material is preferably silicon particles, particles having a structure in which fine silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≦x≦1.6), or a mixture thereof. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a high capacity, and excellent cycle characteristics can be obtained.

[0273] Silicon oxide in the present disclosure is a general term for amorphous silicon oxide, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≦x≦1.6). x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, which is then cooled and precipitated.

[0274] Particles having a structure in which silicon particles are dispersed in a silicon-based compound can be obtained, for example, by a method of baking a mixture of silicon particles and a silicon-based compound, or by heat treating silicon oxide particles before disproportionation represented by the general formula SiOx in an inert non-oxidizing atmosphere such as argon at a temperature of 400°C or higher, preferably 800 to 1,100°C, to perform a disproportionation reaction. In particular, the material obtained by the latter method is preferable because the silicon microcrystals are uniformly dispersed. The size of the silicon nanoparticles can be made 1 to 100 nm by the above-mentioned disproportionation reaction. Note that the silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. Note that it is possible to confirm that silicon nanoparticles (crystals) are dispersed in amorphous silicon oxide by a transmission electron microscope.

[0275] The physical properties of the silicon-containing particles can be appropriately selected depending on the composite particles to be produced. For example, the average particle size is preferably 0.1 to 50 μm, and the lower limit is more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. The upper limit is more preferably 30 μm or less, and even more preferably 20 μm or less. The average particle size is expressed as the weight average particle size measured by a particle size distribution measurement using a laser diffraction method.

[0276] BET specific surface area is 0.5 to 100 m 2 / g is preferable, and 1 to 20m 2 / g is more preferable. 2 / g or more, there is no risk of the adhesiveness decreasing when processed into an electrode, which may result in a decrease in battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and there is no risk of a decrease in battery capacity when used as a negative electrode material for a lithium ion secondary battery.

[0277] The silicon-containing particles are coated with carbon to impart electrical conductivity, which leads to improved battery characteristics. Methods for imparting electrical conductivity include mixing with conductive particles such as graphite, coating the surfaces of the silicon-containing particles with a carbon coating, and combining both of these methods. The carbon coating method is preferred, and chemical vapor deposition (CVD) is more preferred.

[0278] In order to increase the capacity of the resulting electrode mixture, the content of the negative electrode active material is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more in the electrode mixture, and the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less.

[0279] The electrode mixture of the present disclosure preferably further contains a conductive assistant. Any known conductive material can be used as the conductive assistant. Specific examples include metal materials such as copper and nickel, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF. These may be used alone or in any combination and ratio of two or more.

[0280] The conductive assistant is used in an electrode mixture so that it is contained in an amount of usually 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less. If the content is lower than this range, the conductivity may be insufficient. Conversely, if the content is higher than this range, the battery capacity may decrease.

[0281] The electrode mixture of the present disclosure may further contain a thermoplastic resin. Examples of the thermoplastic resin include polyvinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polyethylene oxide, etc. One type may be used alone, or two or more types may be used in any combination and ratio.

[0282] The ratio of the thermoplastic resin to the electrode active material is usually 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and usually 3.0% by mass or less, preferably 2.5% by mass or less, more preferably 2.0% by mass or less. The addition of the thermoplastic resin can improve the mechanical strength of the electrode. If the ratio exceeds this range, the ratio of the electrode active material in the electrode mixture decreases, which may cause problems such as a decrease in the battery capacity or an increase in the resistance between the active materials.

[0283] In the electrode mixture of the present disclosure, the content of the binder may be 0.1% by mass or more, preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and may be 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, particularly preferably 5% by mass or less, and most preferably 3% by mass or less. If the proportion of the binder is too low, the electrode mixture active material cannot be sufficiently held, and the mechanical strength of the electrode mixture sheet may be insufficient, which may deteriorate the battery performance such as cycle characteristics. On the other hand, if the proportion is too high, it may lead to a decrease in battery capacity and conductivity. Since the binder of the present disclosure has excellent binding strength, even if the content is small, the electrode active material can be sufficiently held.

[0284] In the electrode mixture of the present disclosure, the binder component is preferably substantially composed of the PTFE, and more preferably is composed of the PTFE. The binder component is substantially composed of the PTFE, which means that the content of the PTFE in the binder component constituting the electrode mixture is 95.0% by mass or more relative to the binder component. The content of the PTFE is preferably 98.0% by mass or more relative to the binder component, more preferably 99.0% by mass or more, even more preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more.

[0285] The electrode mixture of the present disclosure is preferably in the form of a sheet.

[0286] The electrode mixture of the present disclosure can be suitably used as an electrode mixture for a secondary battery. In particular, the electrode mixture of the present disclosure is suitable for a lithium ion secondary battery. When used in a secondary battery, the electrode mixture of the present disclosure is usually used in a sheet form.

[0287] The electrode mixture sheet has a thickness of preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, particularly preferably 150 μm or less, and preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0288] An example of a specific method for producing an electrode mixture sheet containing an electrode mixture is shown below. The electrode mixture sheet can be obtained by a production method including a step (1) of mixing a raw material composition containing an electrode active material, a binder, and, if necessary, a conductive assistant, a step (2) of forming the raw material composition obtained in the step (1) into a bulk form, and a step (3) of rolling the bulk raw material composition obtained in the step (2) into a sheet form.

[0289] At the stage where the raw material composition is mixed in the above step (1), the raw material composition is present in a state without a fixed shape, with the electrode active material, binder, etc. simply being mixed together. Specific mixing methods include mixing methods using a W-type mixer, V-type mixer, drum mixer, ribbon mixer, conical screw mixer, single-shaft kneader, twin-shaft kneader, mix muller, stirring mixer, planetary mixer, etc.

[0290] In the above step (1), the binder mixing condition is preferably 3000 rpm or less. It is preferably 10 rpm or more, more preferably 15 rpm or more, and even more preferably 20 rpm or more, and is preferably 2000 rpm or less, more preferably 1500 rpm or less, and even more preferably 1000 rpm or less. If it is below the above range, mixing takes a long time, which affects productivity. On the other hand, if it is above the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with poor strength and flexibility.

[0291] In the above step (2), forming into a bulk shape refers to forming the raw material composition into a single mass. Specific methods for forming into a bulk shape include extrusion molding, press molding, and the like. In addition, the "bulk shape" does not specify a particular shape, and may be in the form of a single mass, and includes shapes such as rods, sheets, spheres, and cubes.

[0292] Specific examples of the rolling method in the above step (3) include rolling methods using a roll press, a plate press, a calendar roll machine, or the like.

[0293] It is also preferable to have a step (4) after step (3) in which a larger load is applied to the obtained rolled sheet to roll it into an even thinner sheet. It is also preferable to repeat step (4). In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (4) is preferably 2 to 10 times, and more preferably 3 to 9 times. Specific rolling methods include, for example, a method in which two or more rolls are rotated and the rolled sheet is passed between them to process it into a thinner sheet.

[0294] From the viewpoint of adjusting the fibril diameter, it is also preferable to have a step (5) after the step (3) or the step (4) of roughly crushing the rolled sheet, forming it into a bulk shape again, and rolling it into a sheet. It is also preferable to repeat the step (5). The number of times of the step (5) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0295] In step (5), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include folding the sheet, forming it into a rod or thin sheet shape, chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (3) or step (4) into a different shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0296] In addition, step (4) may be performed after step (5), or may be performed repeatedly. In addition, uniaxial or biaxial stretching may be performed in steps (2), (3), (4), and (5). In addition, the fibril diameter can be adjusted by the degree of crushing in step (5).

[0297] In the above steps (3), (4) or (5), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If it is below the above range, the number of times of rolling increases, which takes time and affects productivity. If it is above the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before rolling. The sample before rolling may be a bulk-shaped raw material composition or a sheet-shaped raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling.

[0298] The electrode mixture sheet is Step (a): mixing a powder component and a binder to form an electrode mixture; Step (b): Calendaring or extrusion molding the electrode mixture to produce a sheet; Including, The mixing in step (a) is (a1) homogenizing the powder components and the binder to form a powder; (a2) mixing the powdered raw material mixture obtained in step (a1) to prepare an electrode mixture; It can also be suitably produced by a production method comprising the steps of:

[0299] For example, PTFE has two transition temperatures at about 19°C and about 30°C. Below 19°C, PTFE can be easily mixed while still maintaining its shape. However, above 19°C, the structure of the PTFE particles becomes loose and more sensitive to mechanical shear. At temperatures above 30°C, a greater degree of fibrillation occurs.

[0300] For this reason, the homogenization in (a1) is preferably carried out at a temperature of 19°C or lower, preferably from 0°C to 19°C. That is, in such (a1), it is preferable to mix and homogenize while suppressing fibrillation. The subsequent mixing step (a2) is preferably carried out at a temperature of 30° C. or higher to promote fibrillation.

[0301] The above step (a2) is carried out at a temperature of preferably 30°C to 150°C, more preferably 35°C to 120°C, and even more preferably 40°C to 100°C. In one embodiment, the calendaring or extrusion of step (b) above is carried out at a temperature between 30°C and 150°C, preferably between 35°C and 120°C, more preferably between 40°C and 100°C.

[0302] The mixing in the above step (a) is preferably carried out while applying a shear force. Specific mixing methods include methods using a W-type mixer, V-type mixer, drum mixer, ribbon mixer, conical screw mixer, single-shaft kneader, twin-shaft kneader, Mix Muller, stirring mixer, planetary mixer, Henschel mixer, high-speed mixer, etc.

[0303] The mixing conditions may be appropriately set by the number of revolutions and the mixing time. For example, the number of revolutions is preferably 15,000 rpm or less. It is preferably 10 rpm or more, more preferably 50 rpm or more, and even more preferably 100 rpm or more, and is preferably 12,000 rpm or less, more preferably 10,000 rpm or less, and even more preferably 8,000 rpm or less. If it is below the above range, it will take a long time to mix, which will affect productivity. If it is above the above range, fibrillation will proceed excessively, and the electrode mixture sheet may have poor strength. The step (a1) is preferably carried out with a weaker shear force than the step (a2). Moreover, it is preferable that step (a1) is carried out for a shorter time than step (a2).

[0304] In the above step (a2), the raw material composition preferably does not contain a liquid solvent, but a small amount of a lubricant may be used. That is, a lubricant may be added to the powdered raw material mixture obtained in the above step (a1) to prepare a paste.

[0305] The lubricant is not particularly limited, and examples thereof include water, ether compounds, alcohols, ionic liquids, carbonates, aliphatic hydrocarbons (low polarity solvents such as heptane and xylene), isoparaffinic hydrocarbon compounds, and petroleum fractions (gasoline (C4-C10), naphtha (C4-C11), kerosene / paraffin (C10-C16), and mixtures thereof).

[0306] The lubricant preferably has a water content of 1000 ppm or less. A moisture content of 1000 ppm or less is preferable in terms of reducing deterioration of the electrochemical device, and the moisture content is more preferably 500 ppm or less.

[0307] When the above-mentioned lubricant is used, it is particularly preferable that the lubricant is a solvent having low polarity, such as butyl butyrate, or an ether compound.

[0308] When the above lubricant is used, the amount thereof may be 5.0 to 35.0 parts by weight, preferably 10.0 to 30.0 parts by weight, and more preferably 15.0 to 25.0 parts by weight, based on the total weight of the composition used in step (a1).

[0309] It is preferable that the raw material composition does not substantially contain a liquid medium. In the conventional electrode mixture forming method, a solvent in which a binder is dissolved is used to prepare a slurry in which powder, which is an electrode mixture component, is dispersed, and the electrode mixture sheet is prepared by applying and drying the slurry. In this case, a solvent that disperses or dissolves the binder is used. However, the solvent that can dissolve the binder resin that has been generally used in the past is limited to a specific solvent such as N-methylpyrrolidone. Since the solvent has high polarity and requires a drying process, the use of the solvent generates processes and costs. In addition, these react with electrolytes such as electrolytic solutions and solid electrolytes to deteriorate the electrolyte, so that the residual components during slurry preparation or after drying may cause a decrease in battery performance. In addition, the binder resin that dissolves in low polarity solvents such as heptane is very limited, and the flash point is low, making handling complicated.

[0310] By using a powder binder with low moisture content without using a solvent when forming the electrode mixture sheet, a battery with little electrolyte deterioration can be manufactured. Furthermore, in the above-mentioned manufacturing method, an electrode mixture sheet containing a binder having a fine fiber structure can be manufactured, and by not preparing a slurry, the burden of the manufacturing process can be reduced.

[0311] Step (b) is calendering or extrusion. Calendering and extrusion can be performed by a known method. By this, it is possible to form the electrode mixture sheet into a shape. The step (b) preferably includes the steps of (b1) forming the electrode mixture obtained in the step (a) into a bulk form, and (b2) calendaring or extrusion molding the bulk form of the electrode mixture.

[0312] Forming into a bulk form means forming the electrode mixture into a single mass. Specific methods for forming the material into a bulk form include extrusion molding, press molding, and the like. In addition, the term "bulk" does not specify a particular shape, and may refer to a state in which the material is in the form of a single mass, including rods, sheets, spheres, cubes, etc. The size of the mass is preferably such that the diameter or the smallest side of the cross section is 10,000 μm or more, more preferably 20,000 μm or more.

[0313] A specific example of the calendering or extrusion molding method in the above step (b2) is a method in which the electrode mixture is rolled using a roll press machine, a calender roll machine or the like.

[0314] The above step (b) is preferably carried out at 30 to 150° C. As described above, PTFE has a glass transition temperature around 30° C., and therefore is easily fibrillated at temperatures of 30° C. or higher. Therefore, the step (b) is preferably carried out at such a temperature.

[0315] And, calendaring or extrusion applies a shear force, which fibrillates the PTFE and forms it into a shape.

[0316] It is also preferable to have a step (c) after step (b) in which a larger load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also preferable to repeat step (c). In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (c) is preferably from 2 to 10, and more preferably from 3 to 9. A specific rolling method includes, for example, a method in which a rolled sheet is passed between two or more rotating rolls to process it into a thinner sheet.

[0317] From the viewpoint of adjusting the sheet strength, it is also preferable to have a step (d) after the step (b) or the step (c) of crushing the rolled sheet, forming it into a bulk shape again, and rolling it into a sheet shape. It is also preferable to repeat the step (d). The number of times of the step (d) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0318] In step (d), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include folding the rolled sheet, forming it into a rod or thin sheet shape, chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (b) or (c) into another shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0319] Furthermore, step (c) may be carried out after step (d), or may be carried out repeatedly. Moreover, uniaxial or biaxial stretching may be carried out in steps (a), (b), (c) and (d). Furthermore, the sheet strength can also be adjusted by the degree of coarse crushing in step (d).

[0320] In the above steps (b), (c) or (d), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If the rolling ratio is below the above range, the number of rolling times increases and it takes time, which affects productivity. If the rolling ratio is above the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after rolling to the thickness before rolling. The sample before rolling may be a bulk raw material composition or a sheet-like raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling. The above steps (c) and (d) are preferably carried out at 30° C. or higher, more preferably 60° C. or higher, and preferably at 150° C. or lower.

[0321] The electrode mixture sheet can be used as an electrode mixture sheet for a secondary battery. It can be used for either a negative electrode or a positive electrode. In particular, the electrode mixture sheet is suitable for a lithium ion secondary battery.

[0322] The present disclosure also provides an electrode comprising the above-mentioned PTFE of the present disclosure or the binder of the present disclosure, an electrode active material, and a current collector. The electrode of the present disclosure has a powder component of an electrochemical device uniformly dispersed therein, and is excellent in strength and flexibility. In addition, even if the amount of binder is small, the electrode active material can be held, and therefore, more materials that improve the electrochemical device properties, such as active materials and conductive assistants, can be added.

[0323] The electrode of the present disclosure may include the above-mentioned electrode mixture of the present disclosure (preferably an electrode mixture sheet) and a current collector.

[0324] The electrodes of the present disclosure may be positive electrodes or negative electrodes.

[0325] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0326] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0327] It is also preferable that the surface of the current collector is roughened, from the viewpoint of improving the adhesion between the current collector and the positive electrode active material layer and reducing the electrical contact resistance. The surface roughness of the current collector, expressed as Sa (arithmetic mean height), is preferably about 260 nm or greater, more preferably about 280 nm or greater, and even more preferably about 300 nm or greater.

[0328] In addition, it is also preferable that a conductive assistant is applied to the surface of the current collector in order to reduce the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver. Carbon is particularly preferable in terms of its small weight.

[0329] The positive electrode may be manufactured by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0330] The density of the positive electrode mixture sheet is preferably 2.80 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3The range is as follows. If the thickness exceeds this range, cracks may easily occur in the sheet. If the thickness falls below this range, the conductivity between the active materials decreases, which increases the battery resistance and may prevent high output from being obtained.

[0331] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less, on one side of the current collector.

[0332] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0333] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0334] It is also preferable that the surface of the current collector is roughened, from the viewpoint of improving the adhesion between the current collector and the positive electrode active material layer and reducing the electrical contact resistance. The surface roughness of the current collector, expressed as Sa (arithmetic mean height), is preferably about 260 nm or greater, more preferably about 280 nm or greater, and even more preferably about 300 nm or greater.

[0335] In addition, it is also preferable that a conductive assistant is applied to the surface of the current collector in order to reduce the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver. Carbon is particularly preferable in terms of its small weight.

[0336] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0337] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the thickness exceeds this range, cracks may easily occur in the sheet. If the thickness falls below this range, the conductivity between the active materials decreases, which increases the battery resistance and may prevent high output from being obtained.

[0338] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less on one side of the current collector.

[0339] The present disclosure also provides a secondary battery comprising the electrode of the present disclosure described above.

[0340] The secondary battery of the present disclosure may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0341] The secondary battery using the above-mentioned electrolyte may use electrolytes, separators, etc. that are used in known secondary batteries. These will be described in detail below.

[0342] The electrolyte is preferably a non-aqueous electrolyte, which may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.

[0343] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroether, and fluorinated carbonate can be used.

[0344] Examples of the electrolyte salt include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, and LiN(SO2C2F5)2. From the viewpoint of good cycle characteristics, LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations thereof are particularly preferred.

[0345] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L or less.

[0346] The secondary battery using the above-mentioned electrolyte preferably further includes a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.

[0347] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.

[0348] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.

[0349] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0350] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fluororesin as a binder.

[0351] The material of the exterior case is not particularly limited as long as it is a material that is stable against the electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate film are preferably used.

[0352] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.

[0353] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.

[0354] The solid-state secondary battery is preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based solid-state secondary battery. The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode. In the solid secondary battery, the binder of the present disclosure may be used in the electrode layer or in the solid electrolyte layer. A solid secondary battery mix (preferably a mix sheet) containing the binder and solid electrolyte of the present disclosure, and a solid electrolyte layer (preferably a solid electrolyte layer sheet) containing the binder and solid electrolyte of the present disclosure are also suitable aspects of the present disclosure.

[0355] The solid electrolyte used in the solid secondary battery mixture may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, it has the advantage of being flexible.

[0356] The sulfide-based solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(X=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12 Any one selected from the above, or a mixture of two or more of them, can be used.

[0357] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0358] The oxide-based solid electrolyte is preferably a compound that contains an oxygen atom (O), has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation properties.

[0359] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf(1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 (LLZ), etc. Ceramic materials in which elements have been substituted for LLZ are also known. For example, Li 6.24 La3Zr2Al 0.24 O 11.98 , Li 6.25 Al 0.25 La3Zr2O 12 and Li substituted with Ta 6.6 La3Zr 1.6 Ta 0.4 O 12 , Li substituted with Nb 6.75 La3Zr 1.75 Nb 0.25 O 12Other examples include LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) is substituted for LLZ. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON, LiPOD, in which part of the oxygen in lithium phosphate is substituted with nitrogen, etc. 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0360] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0361] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the garnet type is preferred.

[0362] The volume average particle diameter of the oxide-based solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, and more preferably 0.03 μm or more. The upper limit is preferably 100 μm or less, and more preferably 50 μm or less. The average particle diameter of the oxide-based solid electrolyte particles is measured by the following procedure. The oxide-based solid electrolyte particles are diluted and adjusted to a 1 mass% dispersion in a 20 ml sample bottle using water (heptane in the case of a substance unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasonic waves for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is taken 50 times using a laser diffraction / scattering type particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C using a measurement quartz cell to obtain the volume average particle diameter. For other detailed conditions, etc., refer to the description of JISZ8828:2013 "Particle size analysis - dynamic light scattering method" as necessary. Five samples are prepared for each level and the average value is adopted.

[0363] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0364] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0365] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0366] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0367] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0368] Various physical properties were measured by the following methods.

[0369] <Average primary particle diameter> The PTFE aqueous dispersion was diluted with water until the solid content became 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average primary particle diameter determined by measuring the unidirectional diameter using a transmission electron microscope were measured to prepare a calibration curve. Using this calibration curve, the average primary particle diameter was determined from the measured transmittance of the 550 nm projected light for each sample.

[0370] <Polymer solids concentration> 1 g of the aqueous PTFE dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass (1 g) of the aqueous dispersion was expressed as a percentage and used.

[0371] <Melt fluidity> According to ASTM D1238, the mass of polymer flowing out of a nozzle with an inner diameter of 2.095 mm and a length of 8 mm per 10 minutes was measured at 372°C and a load of 5 kg using a melt indexer. MFR of 0.25 g / 10 min or more was considered to show melt fluidity, and MFR of less than 0.25 g / 10 min was considered not to show melt fluidity.

[0372] <Specific surface area> A mixture of 30% nitrogen and 70% helium was used as the carrier gas, and liquid nitrogen was used for cooling, and measurements were performed by the BET method (flow method, one-point method) based on JIS Z8830. The Macsorb HM Model-1210 was used as the device.

[0373] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.

[0374] <Median diameter (d50)> The median diameter of the PTFE powder was determined by the following laser diffraction method. The method was carried out in a dry state using a HELOS&RODOS system (product name, manufactured by SYMPATEC). The powder to be measured was dispersed with compressed air at a dispersion pressure of 2 bar, and the shadow of the powder to be measured projected by a laser was detected by the measurement sensor unit to calculate the particle size distribution of the powder to be measured, and the average particle size (50% cumulative particle size) d50 was determined on a volume basis. d50 was set to be equal to the particle size corresponding to 50% of the cumulative particle size distribution.

[0375] <Modified monomer content> The PPVE content was determined by press-molding PTFE powder to produce a thin film disk, measuring the infrared absorbance of the thin film disk using FT-IR. -1 Absorbance at / 935cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at

[0376] <Presence or absence of PTFE particles with a particle size of 1 μm or more> The presence or absence of PTFE particles with a particle size of 1 μm or more was confirmed by measuring the particle size of the PTFE particles through observation using a scanning electron microscope (SEM). The particle size was determined by taking an SEM image of the PTFE powder at a magnification of 2000 times and measuring the distance between two horizontal parallel lines that sandwiched the particle.

[0377] <Content of PTFE including PTFE particles with a particle size of 1 μm or more> About 5 g of PTFE powder was separated into particles obtained by emulsion polymerization and particles obtained by suspension polymerization, and the mass of the particles obtained by emulsion polymerization and the mass of the particles obtained by suspension polymerization were measured, and the PTFE content with a particle diameter of 1 μm or more was calculated according to the following formula. Samples were taken three times, and the average was calculated after each calculation, and the average value was adopted. In addition, according to the above-mentioned particle size measurement method, it was confirmed that the particles obtained by suspension polymerization did not contain PTFE particles with a particle diameter of less than 1 μm. The distinction between the PTFE powder obtained by suspension polymerization and the PTFE powder obtained by emulsion polymerization is clear to those skilled in the art. Content of PTFE including PTFE particles with a particle size of 1 μm or more (mass%) = (mass (g) of particles obtained by suspension polymerization) / [(mass (g) of particles obtained by suspension polymerization)+(mass (g) of particles obtained by emulsion polymerization)]×100

[0378] <Specific surface area 0.5m 2 / g or more 7.0m 2 / g or less of PTFE and PTFE obtained by suspension polymerization > The content of PTFE containing PTFE particles with a particle size of 1 μm or more was determined in the same manner as above. 2 / g or more 7.0m 2 The content of PTFE less than 1 μm / g and the content of PTFE obtained by suspension polymerization are equal to the content of PTFE containing PTFE particles having a particle size of 1 μm or more.

[0379] <Endothermic peak temperature> The endothermic peak temperature was determined as the temperature corresponding to the minimum point on the heat of fusion curve when a PTFE powder that had not been heated to a temperature of 300° C. or higher was heated at a rate of 10° C. / min using a differential scanning calorimeter (DSC). When there were two or more minimum points, the temperature corresponding to the smallest value was determined as the endothermic peak temperature.

[0380] <Can the paste be extruded?> 60 g of PTFE powder and 12.3 g of hydrocarbon oil (trade name: Isopar G (registered trademark), manufactured by ExxonMobil Corporation) as an extrusion aid were mixed in a polyethylene container for 3 minutes. The above mixture was filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 0.47 MPa was applied to the piston inserted into the cylinder and held for 1 minute. Next, the mixture was extruded from the orifice at a ram speed of 20 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice was 100. If the bead broke and could not be extruded continuously, it was judged as not extrudable, and if the bead did not break and could be extruded continuously, it was judged as extrudable.

[0381] <Moisture content> About 20 g of PTFE powder was heated at 150° C. for 2 hours, the mass was measured before and after, and the mass was calculated according to the following formula. A sample was taken three times, and the mass was calculated for each time, and the average value was calculated. Moisture content (mass%) = [(mass (g) of PTFE powder before heating) - (mass (g) of PTFE powder after heating)] / (mass (g) of PTFE powder before heating) x 100

[0382] <Content of perfluoroether carboxylic acids A and B> 1 g of PTFE powder was weighed, 10 g (12.6 ml) of methanol was added, and ultrasonic treatment was performed for 60 minutes to obtain an extract. The obtained extract was measured by LC / MS / MS. The fluorine-containing compounds in the extract were measured using a liquid chromatograph mass spectrometer (Waters, LC-MS ACQUITY UPLC / TQD). The measurement equipment configuration and LC-MS measurement conditions are shown in Table 1. Using an aqueous solution of a fluorine-containing compound with a known concentration, aqueous solutions with five or more levels of content were prepared, and LC / MS analysis was performed on the aqueous solutions with each content. The relationship between the content and the area area relative to the content was plotted to draw a calibration curve. Using the above calibration curve, the area area of ​​the LC / MS chromatogram of the fluorine-containing compound in the extract was converted to the content of the fluorine-containing compound. The lower detection limit in this measurement method is 10 ppb by mass. [Table 1]

[0383] A white solid A (perfluoroether carboxylic acid A ammonium salt) was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.

[0384] The following fluorine-containing surfactants having a molecular weight of 1,000 or less were prepared. Perfluoroether carboxylic acid B ammonium salt: Fujifilm Wako Pure Chemical Industries, Ltd., Ammonium perfluoro(2-methyl-3-oxahexanoate), structural formula: CF3CF2CF2OCF(CF3)COONH4 The following hydrophilic monomers were prepared: Hydrophilic monomer: Ammonium 2,3,3,3-tetrafluoro-2-[(1,1,2-trifluoro-2-propenyl)oxy]- Propanoate, structural formula: CH2=CFCF2OCF(CF3)COONH4

[0385] Synthesis Example 1 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3480 g of deionized water, 100 g of paraffin wax, and 5.3 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 15.0 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 400 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached about 1200 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 310 nm, and the solid content concentration was 25.3 mass%.

[0386] Manufacturing Example 1 The PTFE aqueous dispersion obtained in Synthesis Example 1 was diluted to a solids concentration of 13% by mass, and the PTFE was solidified while stirring in a container, and then the water was separated by filtration to obtain a wet PTFE powder. The obtained wet PTFE powder was placed on a stainless steel mesh tray (amount placed: 2.0 g / cm 2) and the mesh tray was heat-treated in a hot air circulating electric furnace at 180° C. After 20 hours, the mesh tray was taken out and cooled in air, and then PTFE powder 1 was obtained. The obtained PTFE powder 1 did not exhibit melt flowability. The specific surface area was 7.5 m 2 / g, SSG was 2.156, it did not contain PTFE with a particle size of 1 μm or more, the endothermic peak temperature was 345° C., paste extrusion was possible, the moisture content was 0.000 mass%, and the perfluoroether carboxylic acid A content was less than 10 ppb by mass.

[0387] Synthesis Example 2 A PTFE aqueous dispersion was obtained in the same manner as in Synthesis Example 1, except that 5.3 g of the white solid A was changed to 15.75 g of perfluoroether carboxylic acid B ammonium salt and 35 mg of the hydrophilic monomer. The average primary particle diameter of the obtained PTFE aqueous dispersion was 295 nm, and the solid content concentration was 26.5 mass%.

[0388] Manufacturing Example 2 The PTFE aqueous dispersion obtained in Synthesis Example 2 was diluted to a solids concentration of 13% by mass, and the PTFE was solidified while stirring in a container, and then the mixture was filtered from the water to obtain a wet PTFE powder. The obtained PTFE wet powder was placed on a flat tray (a tray with no air permeability at the bottom and sides), and the flat tray was heat-treated in a hot air circulating electric furnace at 145° C. After 18 hours, the flat tray was removed and cooled in air, and then PTFE powder 2 was obtained. The obtained PTFE powder 2 did not exhibit melt flowability. The specific surface area was 7.5 m 2 / g, SSG was 2.159.

[0389] Preparation example 1 Polymerization of tetrafluoroethylene was carried out by the method described in Production Example 4 of International Publication No. 03 / 035724. In the polymerization, no fluorine-containing surfactant was used. The obtained PTFE suspension polymerization particles were taken out, washed with pure water, and coarsely pulverized to obtain coarsely pulverized particles. The obtained coarsely pulverized particles were air-dried, and the dried coarsely pulverized particles were pulverized by an air jet mill to obtain PTFE powder 3. The obtained PTFE powder 3 did not exhibit melt flowability. The specific surface area was 2.3 m 2 / g, SSG was 2.154, median diameter was 49 μm, it contained PTFE particles with a particle diameter of 1 μm or more, the PTFE content including PTFE particles with a particle diameter of 1 μm or more was 100 mass%, the endothermic peak temperature was 337°C, paste extrusion was not possible, and the moisture content was 0.000 mass%.

[0390] Example 2 Polymerization of tetrafluoroethylene was carried out by the method described in Production Example 2 of International Publication No. 03 / 035724. In the polymerization, the amount of perfluoro(propyl vinyl ether) charged was 85 g, and no fluorine-containing surfactant was used. The obtained PTFE suspension polymerization particles were taken out, washed with pure water, and coarsely pulverized to obtain coarsely pulverized particles. The obtained coarsely pulverized particles were air-dried, and the dried coarsely pulverized particles were pulverized in an air jet mill to obtain PTFE powder 4. The obtained PTFE powder 4 did not exhibit melt flowability. The specific surface area was 1.9 m 2 / g, SSG was 2.150, the PPVE modification amount was 0.08% by mass, the median diameter was 19 μm, it contained PTFE particles with a particle diameter of 1 μm or more, the PTFE content including PTFE particles with a particle diameter of 1 μm or more was 100% by mass, the endothermic peak temperature was 340°C, the paste could not be extruded, and the moisture content was 0.000% by mass.

[0391] Preparation example 3 Polymerization of tetrafluoroethylene was carried out by the method described in Production Example 3 of International Publication No. 03 / 035724. In the polymerization, perfluoro(propyl vinyl ether) was not used, and 1.0 g of a fluorine-containing surfactant was charged. The obtained PTFE suspension polymerization particles were taken out, washed with pure water, and coarsely pulverized to obtain coarsely pulverized particles. The obtained coarsely pulverized particles were air-dried, and the dried coarsely pulverized particles were pulverized in an air jet mill to obtain PTFE powder 5. The obtained PTE powder 5 did not exhibit melt flowability. The specific surface area was 2.4 m 2 / g, SSG was 2.159, median diameter was 55 μm, it contained PTFE particles with a particle diameter of 1 μm or more, the PTFE content including PTFE particles with a particle diameter of 1 μm or more was 100 mass%, the endothermic peak temperature was 345°C, paste extrusion was not possible, and the moisture content was 0.000 mass%.

[0392] Preparation Example 4 PTFE powder 6 was obtained by mixing PTFE powder 1 obtained in Production Example 1 and PTFE powder 3 obtained in Preparation Example 1 in a mass ratio (PTFE powder 1:PTFE powder 3) of 10:90. The obtained PTFE powder 6 did not exhibit melt flowability. The specific surface area was 2.7 m 2 / g, SSG was 2.156, it contained PTFE particles with a particle size of 1 μm or more, the PTFE content including PTFE particles with a particle size of 1 μm or more was 89 mass%, the endothermic peak temperature was 337°C, paste extrusion was not possible, the moisture content was 0.000 mass%, and the perfluoroether carboxylic acid A content was less than 10 ppb by mass.

[0393] Preparation example 5 PTFE powder 7 was obtained in the same manner as in Preparation Example 4, except that the mass ratio of the PTFE powders was changed to 30:70. The obtained PTFE powder 7 did not exhibit melt flowability. The specific surface area was 3.7 m 2 / g, SSG was 2.156, it contained PTFE particles with a particle size of 1 μm or more, the PTFE content including PTFE particles with a particle size of 1 μm or more was 69 mass%, the endothermic peak temperature was 337°C, paste extrusion was not possible, the moisture content was 0.000 mass%, and the perfluoroether carboxylic acid A content was less than 10 ppb by mass.

[0394] Preparation Example 6 PTFE powder 8 was obtained in the same manner as in Preparation Example 4, except that the mass ratio of the PTFE powders was changed to 50:50. The obtained PTFE powder 8 did not exhibit melt flowability. The specific surface area was 4.4 m 2 / g, SSG was 2.156, it contained PTFE particles with a particle size of 1 μm or more, the PTFE content including PTFE particles with a particle size of 1 μm or more was 49 mass%, the endothermic peak temperature was 345°C, paste extrusion was not possible, the moisture content was 0.001 mass%, and the perfluoroether carboxylic acid A content was less than 10 ppb by mass.

[0395] Preparation Example 7 PTFE powder 9 was obtained in the same manner as in Preparation Example 4, except that the mass ratio of the PTFE powders was changed to 60:40. The obtained PTFE powder 9 did not exhibit melt flowability. The specific surface area was 5.2 m 2 / g, SSG was 2.156, it contained PTFE particles with a particle size of 1 μm or more, the PTFE content including PTFE particles with a particle size of 1 μm or more was 42 mass%, the endothermic peak temperature was 345°C, paste extrusion was not possible, the moisture content was 0.001 mass%, and the perfluoroether carboxylic acid A content was less than 10 ppb by mass.

[0396] Example 8 The wet powder obtained in Production Example 1 was placed on a flat tray (a tray with no air permeability on the bottom and sides), and the flat tray was heat-treated in a hot air circulating electric furnace at 180° C. After 5 hours, the flat tray was removed and cooled in air, and then PTFE powder 10 was obtained. The resulting PTFE powder 10 did not exhibit melt flowability. The specific surface area was 7.5 m 2 / g, SSG was 2.156, it did not contain PTFE with a particle size of 1 μm or more, the endothermic peak temperature was 345°C, the paste could be extruded, and the moisture content was 0.126 mass%.

[0397] Example 9 The PTFE powder 2 obtained in Production Example 2 and the PTFE powder 3 obtained in Preparation Example 1 were mixed in a mass ratio (PTFE powder 2:PTFE powder 3) of 30:70 to obtain PTFE powder 11. The obtained PTFE powder 11 did not exhibit melt flowability. The specific surface area was 3.7 m 2 / g, SSG was 2.156, it contained PTFE particles with a particle size of 1 μm or more, the PTFE content including PTFE particles with a particle size of 1 μm or more was 68 mass%, the endothermic peak temperature was 337°C, paste extrusion was not possible, the moisture content was 0.005 mass%, and the perfluoroether carboxylic acid B content was 48 ppb by mass.

[0398] Each of the PTFE powders obtained above was evaluated by the following methods.

[0399] The supply stability of Examples 1 to 8 and Comparative Examples 1 and 2 was evaluated according to the following procedure. <Supply stability evaluation> About 50 g of PTFE powder was put into a powder weighing feeder (PSF-100SA, AS ONE Corporation), feeding was performed at a rotation speed of 60 rpm, the discharged amount from the feeder was measured, and the recovery rate was calculated according to the following formula. Feeding was performed three times, and the average was calculated for each, and the average value was adopted. Recovery rate (%) = (discharge from the feeder (g)) / (feed into the feeder (g)) x 100 The supply stability of each PTFE powder was evaluated according to the following criteria. A: Recovery rate of 90% or more B: Recovery rate between 75% and 90% C: Recovery rate less than 75% The results are shown in Table 2.

[0400] [Table 2]

[0401] The mixture sheets and electrodes of Examples 9 to 16 and Comparative Examples 3 and 4 were produced according to the following procedure. <Preparation of positive electrode mixture sheet> The active material and conductive additive were weighed, and the materials were put into a V-type mixer and mixed at 37 rpm for 10 minutes to obtain a mixture of the active material and conductive additive. Then, the weighed binder (PTFE powder) was put into the mixture and it was cooled sufficiently in a thermostatic bath at 5°C. The mixture of the active material, conductive additive and binder was put into a Henschel mixer and homogenized by processing at 1000 rpm for 3 minutes. The mixture was then sufficiently heated in a thermostatic bath at 100°C, and then treated for 5 minutes (32 rpm, heater 50°C, pressure 0.5 MPa) in a pressure kneader (D1-5: manufactured by Nihon Spindle Co., Ltd.) to promote fibrillation and obtain a bulk electrode mixture with cohesive properties. The bulk electrode mixture was then placed in a Henschel mixer for re-pulverization, and treated at 300 rpm for 2 minutes to obtain an electrode mixture. The electrode mixture was placed between parallel metal rolls (temperature: 100°C, rotation speed: 1 m / min) and rolled to obtain an electrode mixture sheet. The rolled sheet obtained was again folded in half to be roughly crushed, and the electrode mixture was placed between metal rolls (temperature: 80°C, rotation speed: 1 m / min) and rolled to obtain a stronger electrode mixture sheet. Thereafter, the electrode mixture sheet was placed in a roll press machine and the gap was adjusted. The final thickness of the positive electrode mixture layer was adjusted to 90 μm, and a free-standing film was obtained. Table 3 shows the material types and compositions.

[0402] [Table 3] denka Li-400: Carbon black manufactured by Denka

[0403] <Preparation of positive electrode> The above positive electrode mixture sheet was adhered to 20 μm aluminum foil as follows. The adhesive used was a slurry of polyvinylidene fluoride (PVDF) dissolved in N-methylpyrrolidone (NMP) and carbon black dispersed in a ratio of 80:20. The adhesive was applied to aluminum foil and dried on a hot plate at 120°C for 15 minutes to form a current collector with an adhesive layer. Thereafter, the positive electrode mixture sheet was placed on the current collector with the adhesive layer, and the positive electrode mixture sheet and the current collector were bonded together using a roll press machine heated to 100° C. to obtain an electrode.

[0404] <Evaluation of poor dispersion> The electrodes were attached to a flat plate and illuminated diagonally with an LED light. The result was visually confirmed. If there are agglomerates of the conductive additive due to poor dispersion, black streaks will be seen. In Comparative Examples 3 and 4, many black streaks were observed, but in Example 12, no black streaks were visually observed.

Claims

1. Polytetrafluoroethylene used in a binder for an electrochemical device, Specific surface area is 0.5m 2 / g or more 7.0m 2 / g or less.

2. Specific surface area is 1.5m 2 / g or more 5.5m 2 2. The polytetrafluoroethylene according to claim 1, having a standard specific gravity of 2.150 or more and 2.160 or less.

3. A binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 / g or less.

4. The specific surface area of ​​the polytetrafluoroethylene is 1.5 m 2 / g or more 5.5m 2 4. The binder for electrochemical devices according to claim 3, having a standard specific gravity of 2.150 or more and 2.160 or less.

5. Polytetrafluoroethylene used in a binder for an electrochemical device, Specific surface area 0.5m 2 / g or more 7.0m 2 Polytetrafluoroethylene containing 40 mass% or more of polytetrafluoroethylene with a molecular weight of less than 1 / g.

6. Specific surface area 0.5m 2 / g or more 7.0m 2 6. The polytetrafluoroethylene according to claim 5, which contains 40 mass % or more of polytetrafluoroethylene with a molecular weight of less than 1 / g and has a standard specific gravity of 2.150 or more and 2.160 or less.

7. A binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 1. A binder for electrochemical devices comprising 40 mass % or more of polytetrafluoroethylene having a molecular weight of less than 1 / g.

8. The polytetrafluoroethylene has a specific surface area of ​​0.5 m 2 / g or more 7.0m 2 8. The binder for electrochemical devices according to claim 7, which contains 40 mass % or more of polytetrafluoroethylene with a molecular weight of less than 1.0 / g and has a standard specific gravity of 2.150 or more and 2.160 or less.

9. Polytetrafluoroethylene used in a binder for an electrochemical device, Polytetrafluoroethylene containing 40 mass % or more of polytetrafluoroethylene obtained by suspension polymerization.

10. A binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene is a binder for electrochemical devices containing 40 mass % or more of polytetrafluoroethylene obtained by suspension polymerization.

11. Polytetrafluoroethylene used in a binder for an electrochemical device, Polytetrafluoroethylene containing 40 mass % or more of polytetrafluoroethylene containing polytetrafluoroethylene particles having a particle diameter of 1 μm or more.

12. 12. The polytetrafluoroethylene according to claim 9 or 11, having a standard specific gravity of 2.150 or more and 2.160 or less.

13. A binder for electrochemical devices consisting essentially of polytetrafluoroethylene, The polytetrafluoroethylene is a binder for electrochemical devices containing 40 mass % or more of polytetrafluoroethylene containing polytetrafluoroethylene particles having a particle diameter of 1 μm or more.

14. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is polytetrafluoroethylene that does not exhibit melt flowability.

15. 14. The binder for electrochemical devices according to claim 3, wherein the polytetrafluoroethylene has an endothermic peak temperature of 333° C. or higher.

16. 14. The binder for electrochemical devices according to claim 3, 7, 10 or 13, wherein the polytetrafluoroethylene has a standard specific gravity of 2.130 or more and 2.230 or less.

17. 14. The binder for electrochemical devices according to claim 3, 7, 10 or 13, wherein the polytetrafluoroethylene has a standard specific gravity of 2.150 or more and 2.160 or less.

18. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is polytetrafluoroethylene which does not substantially use a fluorine-containing compound having a molecular weight of 1000 or less during polymerization.

19. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene comprises polytetrafluoroethylene obtained by suspension polymerization.

20. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is not paste-extrudable.

21. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is in the form of a powder.

22. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is substantially free of moisture.

23. 14. The binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, wherein the polytetrafluoroethylene is substantially free of a fluorine-containing compound having a molecular weight of 1,000 or less.

24. 14. An electrode mixture comprising the polytetrafluoroethylene according to claim 1, 2, 5, 6, 9 or 11, or the binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, and an electrode active material.

25. The electrode mixture according to claim 24, which is in the form of a sheet.

26. 14. An electrode comprising the polytetrafluoroethylene according to claim 1, 2, 5, 6, 9 or 11, or the binder for electrochemical devices according to claim 3, 4, 7, 8, 10 or 13, an electrode active material, and a current collector.

27. A secondary battery comprising the electrode according to claim 26.

Citation Information

Patent Citations

  • Thin film for battery electrode, and preparation method thereof

    CN113937284A

  • JP1973018747B1

  • Sheet, electrode and fuel cell

    JP2014112514A

  • Polytetrafluoroethylene powder, binder for electrode, electrode mixture, electrode, and secondary battery

    JP2023051888A

  • Electrolyte system for metal-air batteries and methods of use thereof

    US20130034781A1